Serendipitous insight into pre-hatch microstructure formation in larval lake whitefish (Coregonus clupeaformis) otoliths - K. M. Dawson; M. R. Lowe; J. S. McConnell; B. A. Buechel; A. M. Muir (Environmental Biology of Fishes, 2026)

Seasonal Variability of Residence Time and Ocean Exchange in a Semi-enclosed Gulf in Northwestern Australia - Camille M. Grimaldi; Michael V. W. Cuttler; Johan Reyns; Jessica A. Benthuysen; Carolina Castro-Sanguino; Luke Thomas; James P. Gilmour; Ryan J. Lowe (Estuaries and Coasts, 2026)
Coastal water exchange with the open ocean plays a key role in regulating the transport and distribution of nutrients, heat, pollutants, suspended sediments and organisms in semi-enclosed systems. In this study, we quantify coastal water exchange for Exmouth Gulf (Australian North West Shelf), a globally significant water body adjacent to the Ningaloo Coast World Heritage Area. We use a high-resolution (200 m) hydrodynamic model, along with particle tracking, to quantify the spatiotemporal variation in circulation, water residence times, and export from the Gulf to the adjacent ocean. Water residence times in Exmouth Gulf are primarily influenced by tidal and wind forcing, with wind waves providing an additional, though secondary, contribution. The shortest Gulf residence times occurred in spring (∼52 days) and the longest in winter (∼276 days). Spatially (and across seasons), residence times within specific subregions were shortest near the western entrance (< 1 day), and longest in the southern Gulf (> 49 days). Export to the ocean was strongest during winter (albeit relatively small, accounting for only 5% of all particles), whereas during the rest of the year particles predominantly remained along the wide, shallow continental shelf to the north-east of the Gulf. Connections between the Gulf and the Ningaloo Coast World Heritage Area varied seasonally in strength, reflecting changes in the regional circulation drivers. Overall, the seasonality of regional wind patterns (via surface currents and wind waves) shaped the residence time and export of material and organisms to surrounding areas. We show that wind waves reduce residence times by up to 15% in parts of the Gulf and thus are an important component of system modelling. A thorough understanding of such dynamics is critical to make informed decisions about the conservation and management of the area.

Directed evolution of Gram-negative Klebsiella michiganensis M5al for desiccation tolerance and survivability of a spray-drying encapsulation process - Benjamin M. Arbaugh; Emily M. Makeev; Matthew L. Cope-Arguello; Tiffany M. Lowe-Power; Tina Jeoh (Systems Microbiology and Biomanufacturing, 2026)
Spray drying is a scalable method for producing dry microbial inoculants, but Gram-negative bacteria often exhibit poor survival under desiccation stress. We employed a directed-evolution approach to improve the survivability of diazotroph Klebsiella michiganensis M5al during spray-drying encapsulation in cross-linked alginate microcapsules (CLAMs). Wildtype K. michiganensis M5al was serially passaged through the CLAMs spray-drying process under incrementally increasing selection pressure. Viable cell density in powders improved over 1000-fold compared to baseline, reaching 3.07 × 10 10 CFU/g over the course of the directed evolution experiment. Paired trials confirmed a statistically significant increase in survival of evolved isolates relative to the parental strain (mean difference of 1.39 log 10 , P < 0.05). Whole-genome sequencing and analysis using breseq identified candidate mutations associated with desiccation tolerance, including a single point mutation in the phosphoenolpyruvate carboxylase gene ( pepC ), suggesting a potential link between central carbon metabolism and stress adaptation. These results demonstrate that genetic adaptation can rapidly enhance microbial fitness under industrial drying conditions without modifying formulation, providing a practical strategy for improving the manufacturability and deployment of Gram-negative microbial biostimulants and related products.

Harnessing Citizen Science to Support Nature-Based Flood Management: A Case Study of Photo Post Engagement in the Limb Brook Catchment, Sheffield, UK - Melissa M. Lacey; Cedric Andreasen; Jackie Lowe; John McGlinchey; Patrick Sheard; Claire Bithell; Samuel Lilleker; Martin Reed; Roger Nowell; Rachel Schwartz-Narbonne; Rebecca Sharpe (Environmental Management, 2026)
Nature-based solutions (NBS) are increasingly promoted in climate adaptation strategies to mitigate flood risks and enhance ecosystem resilience. However, the monitoring and evaluation of such interventions remain a challenge due to resource limitations. This paper evaluates a citizen science-based monitoring approach in the Limb Brook catchment (Sheffield, UK), where public photo submissions were used to assess the effectiveness of NBS interventions such as leaky dams and attenuation ponds. Over a 26-month period, over 4500 photographs were collected from 15 fixed photo points. The analysis demonstrates high initial engagement, varied spatial interaction across sites, and the potential for real-time detection of intervention failures. We critically examine how public participation in environmental monitoring can support adaptive flood risk management while highlighting barriers related to data infrastructure, privacy regulations, and long-term community involvement. This study underscores the value of integrating citizen science into national and local policy frameworks for environmental governance.

Biases in simulating Amazon moisture transport: a convection-permitting versus regional climate model intercomparison - Murilo Ruv Lemes; Gilberto Fisch; Lincoln M. Alves; José Augusto Veiga; Gilvan Sampaio; Richard Bassett; Douglas Lowe; Adriane L. Brito; Polyanna da Conceição Bispo (Climate Dynamics, 2026)
The dynamics of moisture transport in the Amazon are key to the South American water cycle. Convection-permitting regional climate models (CPRCMs) offer a valuable tool to better understand these processes. This study evaluates integrated water vapor transport (IVT) and precipitation in the Amazon Basin using a CPRCM simulation during austral summer (DJF) and winter (JJA). Simulations at 4.5 km resolution cover most of South America and are validated using ERA5 reanalysis. The CPRCM-ERA experiment (1998–2007) was driven by ERA-Interim data and downscaled to 25 km with an RCM. During DJF, precipitation was overestimated in the central Amazon (+ 1.0 to + 2.0 mm/day) and underestimated in the northeastern and western Amazon (− 2.5 mm/day). The CPRCM-ERA simulation showed a weaker low-level jet (LLJ) and trade winds. IVT analysis indicated a negative bias in moisture transport over the LLJ region, more pronounced in CPRCM-ERA. This model underestimated moisture inflow by 6.1% and outflow by ~ 20%, while the RCM showed smaller biases (inflow + 0.8%, outflow + 7%). In JJA, biases differed: CPRCM-ERA underestimated moisture inflow by 4.7% and outflow by 4.6%, while RCM overestimated both (inflow + 8.2%, outflow + 7.5%). This study provides a detailed comparison between convection-permitting and parameterized regional climate simulations, highlighting how dynamic and thermodynamic mechanisms shape moisture transport biases across the dry and the wet seasons. By evaluating the processes involved, the analysis clarifies the strengths and limitations of using CPRCMs over the Amazon Basin and offers guidance for improving future high-resolution modeling of the South American hydrological cycle.

Dispersal Propensity and Dispersal Distance Are Genetically Independent Traits in a Stream Salamander - Winsor H. Lowe; Brett R. Addis; Madaline M. Cochrane (Molecular Ecology, 2026)
Empirical understanding of dispersal evolution is limited, due in large part to the complexity of the dispersal process and the difficulty of quantifying dispersal directly. To move ahead, it may help to focus on universal dispersal traits: propensity—the discrete emigration response distinguishing dispersers from non‐dispersers—and distance. In particular, little is known about the evolution of dispersal distance, including whether it is an independent trait subject to selection. We used capture‐recapture data and single nucleotide polymorphism (SNP) genotypes from 1906 salamanders sampled over 10 years to test for independent genetic associations with dispersal propensity and distance. Gyrinophilus porphyriticus is a headwater specialist, and our data are from three hydrologically independent streams in New Hampshire. We quantified dispersal propensities and distances directly with recapture histories and we used principal component analysis of SNP genotypes to derive three orthogonal axes of genetic variation. Of 173 recaptured individuals, 81 were non‐dispersers and 92 were dispersers based on an empirically derived 3‐m threshold distinguishing dispersal from movements within an individual's home range. Dispersal distances ranged from 4 to 1248 m. Dispersal propensity and distance were significantly associated with different axes of genetic variation, indicating that these are independent traits capable of responding to different selective forces. More broadly, these results show that quantifying dispersal propensities and dispersal distances—and explicitly assessing interactions and trade‐offs between these traits—may help to advance understanding of dispersal evolution.

Simulated space radiation exposure leads to long-term changes in molecular signatures of the heart - Mollie A. Brekker; Maya Semel; Ivan Korostenskij; Osanna Krikourian; Kaelyn M.W. Kelly; Julia Santos; Moniece Lowe; Siddhita Mhatre; Janani Iyer; Amber M. Paul; Stephanie Puukila; Joshua S. Alwood; et al. (Life Sciences in Space Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Early Imaging Biomarkers of Cartilage Strain After ACL Reconstruction Predict Patient Pain and Altered Knee Loading - Emily Y. Miller; Timothy Lowe; Hongtian Zhu; Woowon Lee; Pablo F. Argote; Danielle Dresdner; James Kelly; Rachel M. Frank; Eric McCarty; Jonathan Bravman; Daniel Stokes; Nancy C. Emery; et al. (Annals of Biomedical Engineering, 2026)
Purpose To investigate temporal evolution of cartilage strain and relaxometry following ACL reconstruction, and examine associations between MRI metrics, pain, and knee loading patterns during gait as potential early markers of cartilage degeneration. Methods Twenty-five participants (15 female, 10 male; mean age 25.6 years) undergoing ACL reconstruction completed MRI assessments at 6 and 12 month post-surgery, including displacement-encoding MRI (intratissue strain) and quantitative relaxometry (T2, T2*, T1ρ). Pain was evaluated using patient-reported outcome scores. Gait analysis quantified knee adduction moment, knee extension moment, and knee flexion moment at 12 months in a subset of patients. Correlations between MRI metrics in cartilage contact regions, patient-reported outcomes, and knee loading were evaluated. Results Between 6 and 12 month post-reconstruction, increased tibial compressive and transverse strains correlated with worsening pain, while increased tibial shear strain associated with reduced pain and improved outcomes. Participants demonstrating greater symptom improvement exhibited higher knee adduction moments, which associated with favorable compositional changes including decreased femoral T1ρ and decreased tibial hydrostatic strain. Higher knee extension moments associated with increased tibial compressive and hydrostatic strain. Conclusion Cartilage strain and T1ρ changes associate with pain and altered loading patterns, suggesting potential as early post-traumatic osteoarthritis markers. The observed links between knee loading patterns and cartilage structural changes highlight beneficial adaptation of the reconstructed knee to mechanical loading, and potential avenues for early therapeutic (gait-modifiable) intervention. Advanced MRI may enable early identification of at-risk patients following ACL reconstruction.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The influence of colostrum-derived maternal cells on neonatal lamb immune responses to routine management practices - Mohamed A. Donia; James F. Lowe; Federico A. Zuckermann; Brian M. Aldridge (The Veterinary Journal, 2026)

Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Real-Time Acoustic Telemetry Buoys as Tools for Nearshore Monitoring and Management - James M. Anderson; Brian S. Stirling; Patrick T. Rex; Emily A. Spurgeon; Anthony McGinnis; Zachariah S. Merson; Darnell Gadberry; Christopher G. Lowe (Journal of Marine Science and Engineering, 2026)
Acoustic telemetry monitoring for tagged sharks in nearshore waters has become an important tool for beach safety management; however, detection performance can vary widely in shallow, high-energy nearshore environments where management decisions are often most time-sensitive. Real-time acoustic telemetry buoys offer the potential to deliver live detections and system diagnostics, but their performance relative to autonomous bottom-mounted receivers remains poorly evaluated under realistic coastal conditions. We compared the detection efficiency of real-time buoy-mounted acoustic receivers and autonomous bottom-mounted receivers across five nearshore sites in southern California. Using paired long-term reference tag deployments and short-term range tests, we quantified detection probability, effective detection range, and the influence of environmental conditions and receiver placement. Detection performance was evaluated in relation to wind speed, water temperature, receiver tilt, and signal-to-noise ratio. Both buoy-mounted and bottom-mounted receivers maintained high long-term detection efficiency, recovering 77–99% of expected transmissions at 82–250 m. Range tests indicated greater effective detection distances for buoy-mounted receivers, with 50% detection probabilities occurring at approximately 471 m compared to 282 m for bottom-mounted receivers. Receiver placement strongly influenced performance, with surface-mounted receivers outperforming bottom-mounted units regardless of receiver model. Environmental effects on detections were site-specific and variable. Detection probability varied predictably with environmental conditions. Higher SNR increased detection success, particularly for bottom/substrate mounted receivers, while warm water significantly reduced detection probability across placement configuration. These results demonstrate that real-time acoustic telemetry buoys provide reliable detection performance in dynamic nearshore environments while offering key operational advantages, including immediate data access and system diagnostics. The observed relationships demonstrate that receiver performance is dynamic rather than fixed, and that real-time buoy systems therefore represent a practical tool for coastal monitoring programs that require timely information to support adaptive management, public safety, and conservation decision making.

Thematic Layers of Genomic Susceptibility for Conservation Monitoring - Andrew N. Black; Jong Yoon Jeon; Andrew J. Mularo; Natalie M. Allen; Erangi Heenkenda; Julia C. Buchanan‐Schwanke; John W. Bickham; Zachary E. Lowe; J. Andrew DeWoody (Molecular Ecology, 2025)
Population genomics has great potential to inform applied conservation management and associated policy. However, the bioinformatic analyses and interpretation of population genomic datasets can be daunting and difficult to convey to nonspecialists, including on‐the‐ground conservationists that work with many state, federal and international agencies. We think that individual population genomic metrics of interest can be interpolated and ultimately distilled into thematic GIS layers that represent spatiotemporal genomic potential (or conversely, susceptibility) in conservation monitoring. As examples relevant to ongoing conservation efforts, we use introgressive hybridisation and individual heterozygosity to illustrate a conceptual approach for mapping population genomic susceptibility. The general framework of thematic layers could be extended to integrate key genomic metrics (e.g., runs of homozygosity and genomic load) that are relevant to many conservation efforts.

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

Warmer Is Deadlier: A Meta‐Analysis Reveals Increasing Temperatures Accentuate Disease Effects on Fisheries Hosts - Megan M. Tomamichel; Kaitlyn I. Lowe; Kaylee M. H. Arnold; Marc. E. Frischer; Brian J. Irwin; Craig W. Osenberg; Richard J. Hall; James E. Byers (Ecology Letters, 2025)
Rapid warming could drastically alter host–parasite relationships, which is especially important for fisheries crucial to human nutrition and economic livelihoods, yet we lack a synthetic understanding of how warming influences parasite‐induced mortality in these systems. We conducted a meta‐analysis using 266 effect sizes from 52 empirical papers on harvested aquatic species and determined the relationship between parasite‐induced host mortality and temperature and how this relationship was altered by host, parasite, and study design traits. Overall, higher temperatures increased parasite‐induced host mortality; however, the magnitude of this relationship varied. Hosts from the order Salmoniformes experienced a greater increase in parasite‐induced mortality with temperature than the average response to temperature across fish orders. Opportunistic parasites were associated with a greater increase in infected host mortality with temperature than the average across parasite strategies, while bacterial parasites were associated with lower infected host mortality as temperature increased than the average across parasite types. Thus, parasites will generally increase host mortality as the environment warms; however, this effect will vary among systems.

Evaluating Coral Farming Strategies in Mauritius: A Comparative Study of Nursery Types, Biodiversity and Environmental Conditions at Pointe Aux Feuilles and Flic-en-Flac - Nadeem Nazurally; Andrew W. M. Pomeroy; Ryan J. Lowe; Inesh Narayanan; Baruch Rinkevich (Journal of Marine Science and Engineering, 2025)
Climate change and anthropogenic stressors are accelerating coral reef degradation, prompting urgent restoration strategies. This study evaluates the performance of two coral nursery types, floating mid-water nurseries (FNs) and bottom-attached table nurseries (TNs), at two contrasting reef environments in Mauritius: the degraded, high sedimentation site of Flic-en-Flac (FEF) and the more pristine Pointe aux Feuilles (PAF). Coral fragments from Millepora sp., Acropora muricata, Acropora selago, and Pocillopora damicornis were monitored over three years for survivorship, growth, and linear extension rate (LER). Survivorship exceeded 88% in all cases, with Millepora sp. in PAF–TN achieving the highest rate (99.8%) and P. damicornis in FEF–FN the lowest (88%). Growth was greatest at PAF–TN, where Millepora sp. reached a mean length of 27.25 cm and LER of 9.66 mm y−1. In contrast, the same species in FEF–TN averaged only 3.64 cm in length and 3.44 mm y−1 in LER. Environmental conditions including higher turbidity, nitrate, and phosphate at FEF, and higher phytoplankton density at PAF significantly influenced coral performance. We propose a site-specific nursery selection framework, including FNs for high-sediment areas and TNs for protected and biodiverse sites, to support more effective coral farming outcomes in island restoration programs.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

eDNA metabarcoding detection of nearshore juvenile white sharks (Carcharodon carcharias) and prey fish communities - Zachariah S. Merson; Elizabeth E. Jahn; Matthew A. Barnes; Emily A. Spurgeon; Patrick T. Rex; Jack T. Elstner; Yamilla N. Samara Chacon; James M. Anderson; Whitney D. Jones; Christopher G. Lowe (Journal of Experimental Marine Biology and Ecology, 2025)

Prenatal exposure to ambient air pollution and subsequent risk of lower respiratory tract infections in childhood and adolescence: A systematic review - Maxine Pepper; Poliana Rebouças; Ila R. Falcão; Nuria Sanchez Clemente; Rachel Lowe; Rochelle Schneider; Julia M. Pescarini; Gervásio F. dos Santos; Roberto FS. Andrade; Taísa R. Cortes; Otavio T. Ranzani; Elizabeth B. Brickley; et al. (International Journal of Hygiene and Environmental Health, 2025)

Southern Ocean Water Mass method: A new statistical approach using microfossil radiolaria for paleoceanographic insights for the Southwest Pacific sector of the Southern Ocean - V. Lowe; G. Cortese; M. Civel-Mazens; H. Bostock (Quaternary Science Reviews, 2024)

Motion artifacts in capacitive ECG monitoring systems: a review of existing models and reduction techniques - Matin Khalili; Hamid GholamHosseini; Andrew Lowe; Matthew M. Y. Kuo (Medical & Biological Engineering & Computing, 2024)
Current research focuses on improving electrocardiogram (ECG) monitoring systems to enable real-time and long-term usage, with a specific focus on facilitating remote monitoring of ECG data. This advancement is crucial for improving cardiovascular health by facilitating early detection and management of cardiovascular disease (CVD). To efficiently meet these demands, user-friendly and comfortable ECG sensors that surpass wet electrodes are essential. This has led to increased interest in ECG capacitive electrodes, which facilitate signal detection without requiring gel preparation or direct conductive contact with the body. This feature makes them suitable for wearables or integrated measurement devices. However, ongoing research is essential as the signals they measure often lack sufficient clinical accuracy due to susceptibility to interferences, particularly Motion Artifacts (MAs). While our primary focus is on studying MAs, we also address other limitations crucial for designing a high Signal-to-Noise Ratio (SNR) circuit and effectively mitigating MAs. The literature on the origins and models of MAs in capacitive electrodes is insufficient, which we aim to address alongside discussing mitigation methods. We bring attention to digital signal processing approaches, especially those using reference signals like Electrode-Tissue Impedance (ETI), as highly promising. Finally, we discuss its challenges, proposed solutions, and offer insights into future research directions. Graphical abstract

Local coral connections within an atoll reef system underlie reef resilience and persistence - Camille M. Grimaldi; Cal Faubel; Luke Thomas; Ayse D. Sahin; Nicole M. Ryan; Matt Rayson; Rebecca Green; Michael W. Cuttler; Eric A. Treml; Ryan. J. Lowe; James P. Gilmour (Limnology and Oceanography, 2024)
The recovery of isolated reef systems is a complex process that is usually associated with the supply of coral larvae from distant reefs (or large‐scale connectivity). However, a frequently neglected process is the potential for supply within the reef itself (or local connectivity). In this study, we quantify and characterize the role of local connectivity over 21 yr of simulated annual coral spawning on an isolated coral reef atoll using outputs from a high‐resolution biophysical model ( 100 s km) and is exported away from the system. Local dispersal plays a pivotal role in creating a highly‐connected network across the reef, enhancing exchanges of larvae within the same reef patches (local retention), across reef zones (e.g., lagoon, reef flat), and across the larger reef system. Finally, we show that this highly‐connected network exhibits a certain level of robustness, even when exposed to environmental stressors such as thermal‐induced mortality. Our findings highlight the previously overlooked role of local scale dispersal in driving recovery of isolated reef systems and emphasize the importance of targeted local management actions, indicating that efforts directed at enhancing and preserving local connectivity can have a substantial impact on the overall health and resilience of isolated reef ecosystems.

Self-reported previous experiences with sharks and stingrays predict behavioral intentions of tolerance: differential effects of wild versus captive marine predators - Gabriella M. Hancock; Katie D. Dudley; Dede Long; Christopher G. Lowe (Frontiers in Marine Science, 2024)
Previous research has shown that the general population are more likely to learn about certain species groups (such as sharks) from popular media as opposed to their own first-hand experience. Yet, personal encounters with these animals can drastically affect people’s beliefs and behaviors. This study surveyed 380 members of the public to assess their previous experience of encountering sharks and stingrays in the wild as well as at zoos and aquaria, and tested how said experiences influenced their behavioral intentions of tolerance for these particular elasmobranchs. Results indicated that self-reported experience having previously encountered these species groups in the wild was predictive of all assessed behavioral indicators of tolerance for sharks and rays. Self-reported previous encounters with captive animals were predictive of fewer behavioral intentions of tolerance, and only for the tolerance of sharks. Findings reveal the important role that first-hand interaction with these animals plays in humans’ tolerance to coexist and care for these animals and their habitat. Implications for conservation are discussed.

Eating Patterns, Stages of Health Behavior Change, and Blood Pressures of First Responders: A Comparison of Firefighters and Law Enforcement Officers - J. Romanchik-Cerpovicz; B. Melton; M. Keko; K. Lowe-McAlvin (Journal of the Academy of Nutrition and Dietetics, 2024)

Coastal generalized ecosystem model (CGEM) 1.0: Flexible model formulations for simulating complex biogeochemical processes in aquatic ecosystems - Brandon M. Jarvis; John C. Lehrter; Lisa Lowe; Bradley Penta; Yongshan Wan; Melissa Duvall; Cody Simmons; Wilson Melendez; Dong S. Ko (Ecological Modelling, 2024)

Lateral flow paired with RT-LAMP: A speedy solution for Influenza A virus detection in swine - Suzanna M. Storms; Joanna Shisler; Thanh H. Nguyen; Federico A. Zuckermann; James F. Lowe (Veterinary Microbiology, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Modeling nearshore total phosphorus in Lake Michigan using linked hydrodynamic and water quality models - James J. Pauer; Mark D. Rowe; Wilson Melendez; Thomas P. Hollenhorst; Lisa L. Lowe; Peter J. Alsip; Dale M. Robertson; Steven A. Pothoven (Ecological Modelling, 2024)

A framework for physically consistent storylines of UK future mean sea level rise - Matthew D. Palmer; Benjamin J. Harrison; Jonathan M. Gregory; Helene T. Hewitt; Jason A. Lowe; Jennifer H. Weeks (Climatic Change, 2024)
We present a framework for developing storylines of UK sea level rise to aid risk communication and coastal adaptation planning. Our approach builds on the UK national climate projections (UKCP18) and maintains the same physically consistent methods that preserve component correlations and traceability between global mean sea level (GMSL) and local relative sea level (RSL). Five example storylines are presented that represent singular trajectories of future sea level rise drawn from the underlying large Monte Carlo simulations. The first three storylines span the total range of the Intergovernmental Panel on Climate Change (IPCC) Sixth Assessment Report (AR6) likely range GMSL projections across the SSP1-2.6 and SSP5-8.5 scenarios. The final two storylines are based upon recent high-end storylines of GMSL presented in AR6 and the recent literature. Our results suggest that even the most optimistic sea level rise outcomes for the UK will require adaptation of up to 1 m of sea level rise for large sections of coastline by 2300. For the storyline most consistent with current international greenhouse gas emissions pledges and a moderate sea level rise response, UK capital cities will experience between about 1 and 2 m of sea level rise by 2300, with continued rise beyond 2300. The storyline based on the upper end of the AR6 likely range sea level projections yields much larger values for UK capital cities that range between about 3 and 4 m at 2300. The two high-end scenarios, which are based on a recent study that showed accelerated sea level rise associated with ice sheet instability feedbacks, lead to sea level rise for UK capital cities at 2300 that range between about 8 m and 17 m. These magnitudes of rise would pose enormous challenges for UK coastal communities and are likely to be beyond the limits of adaptation at some locations.

From climate perceptions to actions: A case study on coffee farms in Ethiopia - Xenia Gomm; Biruk Ayalew; Kristoffer Hylander; Francesco Zignol; Lowe Börjeson; Ayco J. M. Tack (Ambio, 2024)
Increasing temperatures and shifting precipitation patterns have major consequences for smallholder farmers, especially in the Global South. Our study examined spatial patterns and climatic drivers of farmers' perceptions of climate change, and how these perceptions translated into adaptation actions. We interviewed 56 farmers in southwestern Ethiopia and analyzed ERA5-Land reanalysis climate data from 1971 to 2020. The majority of farmers perceived the recorded temperature increase as well as a decrease and shift in the timing of rainfall. Perceived climate change varied with local climate factors and not with the rate of climate change itself. Farmers' adaptation practices showed associations with local temperature, but not with farmers’ perceptions of climate change. Our findings highlight that even if farmers perceive climate change, perceptions are most common in areas where climate action is already urgent, and perceptions may not translate into adaptation. Thus, targeted and timely information and extension programs are crucial.

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Outbreeding reduces survival during metamorphosis in a headwater stream salamander - Winsor H. Lowe; Brett R. Addis; Madaline M. Cochrane (Molecular Ecology, 2024)
Assessing direct fitness effects of individual genetic diversity is challenging due to the intensive and long‐term data needed to quantify survival and reproduction in the wild. But resolving these effects is necessary to determine how inbreeding and outbreeding influence eco‐evolutionary processes. We used 8 years of capture–recapture data and single nucleotide polymorphism genotypes for 1906 individuals to test for effects of individual heterozygosity on stage‐specific survival probabilities in the salamander Gyrinophilus porphyriticus . The life cycle of G. porphyriticus includes an aquatic larval stage followed by metamorphosis into a semi‐aquatic adult stage. In our study populations, the larval stage lasts 6–10 years, metamorphosis takes several months, and lifespan can reach 20 years. Previous studies showed that metamorphosis is a sensitive life stage, leading us to predict that fitness effects of individual heterozygosity would occur during metamorphosis. Consistent with this prediction, monthly probability of survival during metamorphosis declined with multi‐locus heterozygosity (MLH), from 0.38 at the lowest MLH (0.10) to 0.06 at the highest MLH (0.38), a reduction of 84%. Body condition of larvae also declined significantly with increasing MLH. These relationships were consistent in the three study streams. With evidence of localised inbreeding within streams, these results suggest that outbreeding disrupts adaptations in pre‐metamorphic and metamorphic individuals to environmental gradients along streams, adding to evidence that headwater streams are hotspots of microgeographic adaptation. Our results also underscore the importance of incorporating life history in analyses of the fitness effects of individual genetic diversity and suggest that metamorphosis and similar discrete life stage transitions may be critical periods of viability selection.

Reproducible responses of geochemical and microbial successional patterns in the subsurface to carbon source amendment - Jonathan P. Michael; Andrew D. Putt; Yunfeng Yang; Benjamin G. Adams; Kathryn R. McBride; Yupeng Fan; Kenneth A. Lowe; Daliang Ning; Sindhu Jagadamma; Ji Won Moon; Dawn M. Klingeman; Ping Zhang; et al. (Water Research, 2024)

The influence of micro-scale thermal habitat on the movements of juvenile white sharks in their Southern California aggregation sites - Emily Spurgeon; Marten L. Thompson; Mitchell D. Alexander; James M. Anderson; Patrick T. Rex; Brian Stirling; Kevin Abbott; Christopher G. Lowe (Frontiers in Marine Science, 2024)
While juvenile white sharks (JWS) can display regional endothermy, the need to maintain internal temperatures within an energetically favorable range likely drives thermoregulatory movements to maximize growth and foraging efficiency. Many JWS from the northeastern Pacific population aggregate seasonally in nearshore nursery habitats throughout the Southern California Bight and historic data show that inter-seasonal movement patterns may be heavily dependent on ambient water temperature. However, the degree to which micro-scale (e.g., ~10 m 2 ) water temperature heterogeneity influences JWS three-dimensional movement within nearshore aggregation sites is unknown. High-resolution temperature and passive acoustic-telemetry geo-positional data were used to quantify how temperature and vertical thermal stratification influenced JWS movement using several modeling approaches. JWS selected for water temperatures between 16 – 22°C and depths shallower than 2 m. Sharks occupied deeper waters during dawn and dusk periods, and their distance from the seafloor and spatial orientation of their depth distribution was significantly related to the thermal structure of the water column across the monitored area. Tagged sharks remained above a 16°C thermal threshold and altered their horizontal and vertical distributions accordingly. While high-resolution movement and environmental data provide improved predictability of micro-scale habitat use and distribution, other variables such as prey distribution, behavior, and competition would further improve habitat use models for this highly mobile species.

Connection for conservation: The impact of counting butterflies on nature connectedness and wellbeing in citizen scientists - C.W. Butler; I. Hamlin; M. Richardson; M. Lowe; R. Fox (Biological Conservation, 2024)

Current extent and future opportunities for living shorelines in Australia - Rebecca L. Morris; Erin Campbell-Hooper; Elissa Waters; Melanie J. Bishop; Catherine E. Lovelock; Ryan J. Lowe; Elisabeth M.A. Strain; Paul Boon; Anthony Boxshall; Nicola K. Browne; James T. Carley; Benedikt J. Fest; et al. (Science of The Total Environment, 2024)

Individual growth rates and size at metamorphosis increase with watershed area in a stream salamander - Madaline M. Cochrane; Brett R. Addis; Leah K. Swartz; Winsor H. Lowe (Ecology, 2024)
A fundamental goal of ecology is to understand how the physical environment influences intraspecific variability in life history and, consequently, fitness. In streams, discharge and associated habitat conditions change along a continuum from intermittency to permanence: Headwater streams typically have smaller watersheds and are thus more prone to drying than higher‐order streams with larger watersheds and more consistent discharge. However, few empirical studies have assessed life history and associated population responses to this continuum in aquatic organisms. We tested the prediction that individual growth, rate of development, and population growth increase with watershed area in the long‐lived stream salamander Gyrinophilus porphyriticus , where we use watershed area as a proxy for hydrologic intermittence. To address this hypothesis, we used 8 years of mark–recapture data from 53 reaches across 10 headwater streams in New Hampshire, USA. Individual growth rates and mean size at metamorphosis increased with watershed area for watersheds from 0.12 to 1.66 km 2 . Population growth rates increased with watershed area; however, this result was not statistically significant at our sample size. Mean age of metamorphosis did not vary across watershed areas. Lower individual growth rates and smaller sizes at metamorphosis likely contributed to reduced lifetime fecundity and population growth in reaches with the smallest watershed areas and highest vulnerability to drought. These responses suggest that as droughts increase due to climate change, headwater specialists in hydrologically intermittent environments will experience a reduction in fitness due to smaller body sizes or other growth‐related mechanisms.

Plants, pollinators and their interactions under global ecological change: The role of pollen DNA metabarcoding - Karen L. Bell; Katherine J. Turo; Abigail Lowe; Kevin Nota; Alexander Keller; Francisco Encinas‐Viso; Laura Parducci; Rodney T. Richardson; Richard M. Leggett; Berry J. Brosi; Kevin S. Burgess; Yoshihisa Suyama; et al. (Molecular Ecology, 2023)
Anthropogenic activities are triggering global changes in the environment, causing entire communities of plants, pollinators and their interactions to restructure, and ultimately leading to species declines. To understand the mechanisms behind community shifts and declines, as well as monitoring and managing impacts, a global effort must be made to characterize plant–pollinator communities in detail, across different habitat types, latitudes, elevations, and levels and types of disturbances. Generating data of this scale will only be feasible with rapid, high‐throughput methods. Pollen DNA metabarcoding provides advantages in throughput, efficiency and taxonomic resolution over traditional methods, such as microscopic pollen identification and visual observation of plant–pollinator interactions. This makes it ideal for understanding complex ecological networks and their responses to change. Pollen DNA metabarcoding is currently being applied to assess plant–pollinator interactions, survey ecosystem change and model the spatiotemporal distribution of allergenic pollen. Where samples are available from past collections, pollen DNA metabarcoding has been used to compare contemporary and past ecosystems. New avenues of research are possible with the expansion of pollen DNA metabarcoding to intraspecific identification, analysis of DNA in ancient pollen samples, and increased use of museum and herbarium specimens. Ongoing developments in sequencing technologies can accelerate progress towards these goals. Global ecological change is happening rapidly, and we anticipate that high‐throughput methods such as pollen DNA metabarcoding are critical for understanding the evolutionary and ecological processes that support biodiversity, and predicting and responding to the impacts of change.

Potential ecotoxicological effects of silver nanoparticles and silver sulphide on the endogeic earthworm Aporrectodea caliginosa (Savigny 1826) - Jeannette M. Kister; Christopher N. Lowe; Kevin R. Butt (Ecotoxicology, 2023)
Silver nanoparticles (AgNPs) are increasingly used in consumer products and subsequently arrive in wastewater systems, accumulating as silver sulphide (Ag 2 S) in the resulting biosolids, which are commonly spread onto agricultural fields as a fertiliser. Experiments were performed to investigate the effect of AgNPs, using the endogeic earthworm Aporrectodea caliginosa as a test organism. In an acute toxicity experiment, A. caliginosa were exposed to soil containing different concentrations of AgNPs (0, 1, 5, 10, 50, 100, 250, 500, 750, and 1000 mg kg −1 dry soil) and Ag 2 S (0, 10, 50, 100, 500, and 1000 mg kg −1 dry soil). Earthworm biomass and mortality were monitored. Earthworms exposed to 500, 750 and 1000 mg kg −1 fresh AgNPs had mortality rates of 20%, 60% and 70%, respectively. Changes in biomass were directly related to AgNP concentration. Exposure to Ag 2 S did not affect biomass or mortality. Further experiments used 0, 10, 50, 100 and 250 mg kg −1 AgNPs and 0, 50, 100, 500, and 1000 mg kg −1 Ag 2 S to evaluate sublethal effects on A. caliginosa . Avoidance behaviour in a linear gradient was evaluated after 14 days. Earthworms significantly preferred soil that was free of either AgNPs or Ag 2 S. The same concentrations were used to assess effects on cocoon production of A. caliginosa exposed to AgNPs and Ag 2 S. In the first 3 months of AgNP exposure, higher concentrations had a negative effect on cocoon production, but this effect diminished thereafter. Ag 2 S had no discernible effect on reproduction. Overall, introduction of AgNPs into the soil through the application of biosolids appears to be of low concern to the tested endogeic earthworm.

Evidence of increasing juvenile white sharks ' ( Carcharodon carcharias ) habitat use at the Northern Channel Islands - Ryan M. Freedman; James M. Anderson; Chris Caldow; Brian Stirling; Patrick Rex; Emily Spurgeon; Steve McCullough; Kady Lyons; Jack May; Connor F. White; Ryan K. Logan; Emily Meese; et al. (Journal of Fish Biology, 2023)
Juvenile white sharks ( Carcharodon carcharias ) typically aggregate along coastal beaches; however, high levels of recruitment and shifting oceanographic conditions may be causing habitat use expansions. Telemetry data indicate increased habitat use at the Northern Channel Islands (California, USA) by juvenile white shark that may be in response to increased population density at aggregation locations, or anomalous oceanographic events that impact habitat use or expand available habitat. Findings illustrate the need for long‐term movement monitoring and understanding drivers of habitat use shifts and expansion to improve ecosystem management.

Spatial and temporal variation in toxicity and inorganic composition of hydraulic fracturing flowback and produced water - Connor B. Stewart; Hannah M. Lowes; W. Tyler Mehler; Katherine N. Snihur; Shannon L. Flynn; Daniel S. Alessi; Tamzin A. Blewett (Journal of Hazardous Materials, 2023)

An etiological examination of behavioral intentions to support shark and stingray conservancy: the effects of beliefs in elasmobranchs’ cognitive and affective capacities - Gabriella M. Hancock; Katie D. Dudley; Dede Long; Christopher G. Lowe (Frontiers in Marine Science, 2023)
Keystone species populations, including shark and ray taxonomic groups, are declining due to numerous threats. A better understanding of how individual belief structures inform pro-conservation behavioral intentions is therefore critical to foster support for their conservation and the greater biodiversity of world ecosystems. This study conducted a survey to establish the general public’s cognitive beliefs about the mental and affective capacities of two species groups (sharks and stingrays) known to cause injury to humans, and their effects on different behavioral intentions to support their conservation. Results revealed that a range of different behavioral intentions to support animal conservation are driven by a complex interplay of cognitive beliefs, and some effects were specific to a particular species group while others were not. Beliefs in animals’ cognitive awareness and their emotional abilities were predictive of individuals’ self-reported desire to learn more about the animals and their conservation. Beliefs in animals’ cognitive and emotional capacities were predictive of supporting conservation in terms of voting and donating to their conservation. Finally, beliefs in animals’ reasoning abilities were predictive of different behavioral expressions of tolerance, and support for their conservation via voting only. Despite the potential injurious capabilities of these species, these findings have important implications for educational and conservation programs to emphasize or modify specific beliefs in order to facilitate particular pro-conservation behaviors for maximum benefits to conservation efforts.

Overlapping and distinct relationships between hedonic hunger, uncontrolled eating, food craving, and the obesogenic home food environment during and after a 12-month behavioral weight loss program - Nicole T. Crane; Meghan L. Butryn; Amy A. Gorin; Michael R. Lowe; Erica M. LaFata (Appetite, 2023)

Research priorities for the sustainability of coral-rich western Pacific seascapes - Graeme S. Cumming; Maja Adamska; Michele L. Barnes; Jon Barnett; David R. Bellwood; Joshua E. Cinner; Philippa J. Cohen; Jennifer M. Donelson; Katharina Fabricius; R. Quentin Grafton; Alana Grech; Georgina G. Gurney; et al. (Regional Environmental Change, 2023)
Nearly a billion people depend on tropical seascapes. The need to ensure sustainable use of these vital areas is recognised, as one of 17 policy commitments made by world leaders, in Sustainable Development Goal (SDG) 14 (‘Life below Water’) of the United Nations. SDG 14 seeks to secure marine sustainability by 2030. In a time of increasing social-ecological unpredictability and risk, scientists and policymakers working towards SDG 14 in the Asia–Pacific region need to know: (1) How are seascapes changing? (2) What can global society do about these changes? and (3) How can science and society together achieve sustainable seascape futures? Through a horizon scan, we identified nine emerging research priorities that clarify potential research contributions to marine sustainability in locations with high coral reef abundance. They include research on seascape geological and biological evolution and adaptation; elucidating drivers and mechanisms of change; understanding how seascape functions and services are produced, and how people depend on them; costs, benefits, and trade-offs to people in changing seascapes; improving seascape technologies and practices; learning to govern and manage seascapes for all; sustainable use, justice, and human well-being; bridging communities and epistemologies for innovative, equitable, and scale-crossing solutions; and informing resilient seascape futures through modelling and synthesis. Researchers can contribute to the sustainability of tropical seascapes by co-developing transdisciplinary understandings of people and ecosystems, emphasising the importance of equity and justice, and improving knowledge of key cross-scale and cross-level processes, feedbacks, and thresholds.

Hydrodynamic and atmospheric drivers create distinct thermal environments within a coral reef atoll - C. M. Grimaldi; R. J. Lowe; J. A. Benthuysen; M. V. W. Cuttler; R. H. Green; J. P. Gilmour (Coral Reefs, 2023)
Within coral reefs, different thermal environments can be found at locations separated by less than 100 s of meters and can generate fine-scale patterns of thermal stress and subsequent bleaching. In this study, we use an 11-month record of in situ temperature measurements, coupled with oceanographic and atmospheric data to examine the role of surface and advective heat fluxes in driving spatial patterns of temperature variability across several reef zones (i.e., fore-reef, reef flat, channel and lagoon) within an individual coral reef atoll. We show that advection of heat (driven by a combination of wave and tidal flows) was dominant across all sites and surface heating was more important across shallow areas or areas of low net exchange (i.e., reef flat and lagoon zones). Tidal flows were important in driving short term variability in the transport of heat across the atoll, but their contribution to the net transport of heat (cooling vs heating) was less significant over the longer timescales (days to weeks) that are typically used to assess thermal stress experienced by coral reef communities (e.g., Degree Heating Weeks). Conversely, although the wave-driven advection of heat contributed minimally to reef temperature changes over short timescales, the net transport of heat over daily to weekly timescales had a significant influence on persistent temperature anomalies. By parameterising the mechanisms driving temperature variability across the reef flat and lagoon zones, we demonstrate how satellite measurements of sea surface temperatures can be corrected to provide robust temperature estimates at the reef scale.

Copper exposure does not alter the ability of intertidal sea cucumber Cucumaria miniata to tolerate emersion during low tide - Hannah M. Lowes; Alyssa M. Weinrauch; Ian A. Bouyoucos; Robert A. Griffin; Daniels Kononovs; Daniel S. Alessi; Tamzin A. Blewett (Science of The Total Environment, 2023)

Copper toxicity does not affect low tide emersion tolerance of Mytilus galloprovincialis - Hannah M. Lowes; Erika J. Eliason; Katherine N. Snihur; Daniel S. Alessi; Tamzin A. Blewett (Marine Pollution Bulletin, 2023)

Source–sink dynamics within a complex life history - Winsor H. Lowe; Brett R. Addis; Madaline M. Cochrane; Leah K. Swartz (Ecology, 2023)
Source–sink patch dynamics occur when movement from sources stabilizes sinks by compensating for low local vital rates. The mechanisms underlying source–sink dynamics may be complicated in species that undergo transitions between discrete life stages, particularly when stages have overlapping habitat requirements and similar movement abilities. In these species, for example, the demographic effects of movement by one stage may augment or offset the effects of movement by another stage. We used a stream salamander system to investigate patch dynamics within this form of complex life history. Specifically, we tested the hypothesis that the salamander Gyrinophilus porphyriticus experiences source–sink dynamics in riffles and pools, the dominant geomorphic patch types in headwater streams. We estimated stage‐specific survival probabilities in riffles and pools and stage‐specific movement probabilities between the two patch types using 8 years of capture–recapture data on 4491 individuals, including premetamorphic larvae and postmetamorphic adults. We then incorporated survival and movement probabilities into a stage‐structured, two‐patch model to determine the demographic interactions between riffles and pools. Monthly survival probabilities of both stages were higher in pools than in riffles. Larvae were more likely to move from riffles to pools, but adults were more likely to move from pools to riffles, despite experiencing much lower survival in riffles. In simulations, eliminating interpatch movements by both stages indicated that riffles are sinks that rely on immigration from pools for stability. Allowing only larvae to move stabilized both patch types, but allowing only adults to move destabilized pools due to the demographic cost of adult emigration. These results indicated that larval movement not only stabilizes riffles, but also offsets the destabilizing effects of maladaptive adult movement. Similar patch dynamics may emerge in any structured population in which movement and local vital rates differ by age, size, or stage. Addressing these forms of internal demographic structure in patch dynamics analyses will help to refine and advance general understanding of spatial ecology.

Ula Thirra: a case study in the geomagnetic detection of combustion features in Channel Country of far south-western Queensland - Kelsey M. Lowe; Doug Williams; Nathan Wright; Shawnee Gorringe; Josh Gorringe; Ian Andrews; Meltem Cemre Ustunkaya; Betty Gorringe; Michael C. Westaway (Archaeological and Anthropological Sciences, 2023)

The association of COVID-19 incidence with temperature, humidity, and UV radiation – A global multi-city analysis - Luise Nottmeyer; Ben Armstrong; Rachel Lowe; Sam Abbott; Sophie Meakin; Kathleen M. O'Reilly; Rosa von Borries; Rochelle Schneider; Dominic Royé; Masahiro Hashizume; Mathilde Pascal; Aurelio Tobias; et al. (Science of The Total Environment, 2023)

New Southern Ocean transfer function for subsurface temperature prediction using radiolarian assemblages - M. Civel-Mazens; G. Cortese; X. Crosta; K.A. Lawler; V. Lowe; M. Ikehara; T. Itaki (Marine Micropaleontology, 2023)

Urban forest invertebrates: how they shape and respond to the urban environment - D. Johan Kotze; Elizabeth C. Lowe; J. Scott MacIvor; Alessandro Ossola; Briony A. Norton; Dieter F. Hochuli; Luis Mata; Marco Moretti; Sara A. Gagné; I. Tanya Handa; Therésa M. Jones; Caragh G. Threlfall; et al. (Urban Ecosystems, 2022)
Invertebrates comprise the most diversified animal group on Earth. Due to their long evolutionary history and small size, invertebrates occupy a remarkable range of ecological niches, and play an important role as “ecosystem engineers” by structuring networks of mutualistic and antagonistic ecological interactions in almost all terrestrial ecosystems. Urban forests provide critical ecosystem services to humans, and, as in other systems, invertebrates are central to structuring and maintaining the functioning of urban forests. Identifying the role of invertebrates in urban forests can help elucidate their importance to practitioners and the public, not only to preserve biodiversity in urban environments, but also to make the public aware of their functional importance in maintaining healthy greenspaces. In this review, we examine the multiple functional roles that invertebrates play in urban forests that contribute to ecosystem service provisioning, including pollination, predation, herbivory, seed and microorganism dispersal and organic matter decomposition, but also those that lead to disservices, primarily from a public health perspective, e.g., transmission of invertebrate-borne diseases. We then identify a number of ecological filters that structure urban forest invertebrate communities, such as changes in habitat structure, increased landscape imperviousness, microclimatic changes and pollution. We also discuss the complexity of ways that forest invertebrates respond to urbanisation, including acclimation, local extinction and evolution. Finally, we present management recommendations to support and conserve viable and diverse urban forest invertebrate populations into the future.

A novel method for identifying coded tags recorded on aquatic acoustic monitoring systems - Christopher D. Lowe; Nicolas J. C. Tregenza; Claudia J. Allen; Georgina E. Blow; Hanna Nuuttila; Chiara M. Bertelli; Anouska F. Mendzil; Thomas Stamp; Emma V. Sheehan; Peter Davies; Jonathan C. D. Gordon; Jonathan D. Bolland; et al. (Environmental Monitoring and Assessment, 2022)
Aquatic biotelemetry increasingly relies on using acoustic transmitters (‘tags’) that enable passive detection of tagged animals using fixed or mobile receivers. Both tracking methods are resource-limited, restricting the spatial area in which movements of highly mobile animals can be measured using proprietary detection systems. Transmissions from tags are recorded by underwater noise monitoring systems designed for other purposes, such as cetacean monitoring devices, which have been widely deployed in the marine environment; however, no tools currently exist to decode these detections, and thus valuable additional information on animal movements may be missed. Here, we describe simple hybrid methods, with potentially wide application, for obtaining information from otherwise unused data sources. The methods were developed using data from moored, acoustic cetacean detectors (C-PODs) and towed passive receiver arrays, often deployed to monitor the vocalisations of cetaceans, but any similarly formatted data source could be used. The method was applied to decode tag detections that were found to have come from two highly mobile fish species, bass ( Dicentrarchus labrax ) and Twaite shad ( Alosa fallax ), that had been tagged in other studies. Decoding results were validated using test tags; range testing data were used to demonstrate the relative efficiency of these receiver methods in detecting tags. This approach broadens the range of equipment from which acoustic tag detections can be decoded. Novel detections derived from the method could add significant value to past and present tracking studies at little additional cost, by providing new insights into the movement of mobile animals at sea.

Ice‐sheet deglaciation and Loch Lomond Readvance in the eastern Cairngorms: implications of a Lateglacial sediment record from Glen Builg - Alice Carter‐Champion; Ashley M. Abrook; Joshua H. Pike; Ian P. Matthews; Adrian P. Palmer; J. John Lowe (Journal of Quaternary Science, 2022)
We present new lithostratigraphic, pollen‐stratigraphic and tephrochronological data obtained from a sediment sequence in a small lake basin in Glen Builg, eastern Cairngorms, with mapping of the surrounding glacial geomorphological features. The collective evidence indicates that basin organic sediment accumulation started during the Windermere Interstadial at ~14.3 ka. The new results reaffirm the conclusions of Clapperton et al. (1975), that any occupation of the eastern Cairngorms by Loch Lomond (‘Younger Dryas’) Stadial glacier ice was spatially restricted. The record also suggests that harsh climatic conditions prevailed throughout the Windermere Interstadial, probably due to the relatively high altitude of the site (~460 m) and its proximity to major Cairngorm peaks. Our new, more comprehensive study provides a robust chronology, and reveals several palaeoenvironmental signals congruent with other recently reported Scottish Highlands records. Key similarities with regional records are: (i) a short climatic reversal corresponding to GI‐1d in the Greenland stratotype sequence; (ii) a two‐phased Loch Lomond Stadial, with a transition around the Vedde Ash, dating to ~12.1 ka; and (iii) a delayed response to Early Holocene climatic warming of ~250 years, before soils were sufficiently stabilised to permit shrub vegetation establishment.

Hydrodynamic drivers of fine‐scale connectivity within a coral reef atoll - Camille M. Grimaldi; Ryan J. Lowe; Jessica A. Benthuysen; Michael V. W. Cuttler; Rebecca H. Green; Ben Radford; Nicole Ryan; James Gilmour (Limnology and Oceanography, 2022)
An accurate representation of physical and biological processes is crucial to resolve larval dispersal pathways and characterize connectivity of coral reef ecosystems. We investigate how hydrodynamic forcings drive larval retention rates during the bi‐annual mass coral spawning of the coral genus Acropora within a coral reef atoll (Mermaid Reef), located off northwestern Australia. By analyzing hydrodynamic conditions during 41 yr of historical spring and autumn coral spawning events, we identify typical and extreme hydrodynamic forcing conditions. Particle tracking using the output from a fine‐scale coupled wave‐flow hydrodynamic model forced with typical hydrodynamic conditions during coral spawning, revealed a mean transport of larvae eastward across the atoll. Transport was mainly driven by a combination of wave and tidal currents, where the residual tidal flow and unidirectional wave flow increased the net export of particles, and the oscillatory tidal (non‐residual) flow reduced the net export of particles from the reef. Importantly, however, numerical simulations forced with extreme hydrodynamic conditions generated by episodic tropical cyclones (11 out of 41 yr) showed large deviations from the typical eastward flow during autumn spawning, generating different connectivity pathways within the reef. Considering the substantial time larvae can be retained within reef systems, overlooking fine‐scale hydrodynamic processes may greatly overestimate larval transport distances between adjacent coral reef atolls. As a result, we emphasize the need to consider fine‐scale hydrodynamic processes within regional connectivity predictions, which is generally not considered yet critical to understand the capacity of reefs to recover following disturbances.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Rainfall-driven nutrient loading affects coastal phytoplankton in the southwestern Indian Ocean: a lagoon at Mauritius Island - M Soondur; R Boojhawon; R Lowe; D Kaullysing; BE Casareto; Y Suzuki; R Bhagooli (African Journal of Marine Science, 2022)

Understanding Habitat Fragmentation Between a Full Tidal Bay and a Tidally Restricted Urban Lagoon - Molly K. Burdick-Whipp; Christopher G. Lowe; Alain M. Rosas; Christine R. Whitcraft (Estuaries and Coasts, 2022)

Population genetic structure of a broadcast‐spawning coral across a tropical–temperate transition zone reveals regional differentiation and high‐latitude reef isolation - Richard D. Evans; Luke Thomas; W. Jason Kennington; Nicole M. Ryan; Nerida G. Wilson; Zoe Richards; Ryan J. Lowe; Chenae Tuckett (Journal of Biogeography, 2021)
Aim Genetic connectivity is a key component of species resilience to climate change in terms of recovery capacity following disturbance and capacity to disperse to novel locations as the climate warms and isotherms shift poleward. We aimed to strengthen our understanding of resilience in this context by characterizing patterns of connectivity and genetic diversity in a broadcast spawning coral across a tropical–temperate transition zone. We hypothesize genetic differentiation between tropical and temperate populations and decreasing genetic diversity with higher latitudes. Location Western Australia (WA). Taxon Turbinaria species complex. Turbinaria ‘reniformis’ Oken, 1815 (Scleractinia: Dendrophylliidae). Methods A total of 930 target corals were sampled from 10 locations between 13 and 32° latitude spanning a 9°C mean temperature range. In situ species identification of T . reniformis is hindered by morphological plasticity and homoplasy with sister species. We combined Sanger sequencing of two mitochondrial DNA markers and high‐throughput genotyping by sequencing (GBS) to isolate a single genetic Turbinaria lineage from our dataset through which patterns of genetic flow and diversity along the WA coastline could be explored using population‐ and individual‐based clustering analyses. Results Mitochondrial DNA sequence variation was low among Turbinaria samples and could not resolve individual species. Using GBS, we identified three genetically distinct lineages. Subsequent analyses within one of these lineages revealed strong spatial subdivision with 2–3 genetic clusters. While temperate populations were genetically diverged from more tropical sites, we did not observe declines in genetic diversity with latitude. Main conclusions Tropical populations of T . ‘reniformis’ in Western Australia exhibit strong genetic connectivity, which extends to a southern limit at sub‐tropical Shark Bay. Temperate populations are genetically isolated from their tropical counterparts but have relatively high genetic diversity. While the maintenance of genetic variation in temperate populations may provide some resilience to future climate scenarios, their isolation may increase their vulnerability.

Regional versus latitudinal variation in the life‐history traits and demographic rates of a reef fish, Centropyge bispinosa , in the Coral Sea and Great Barrier Reef Marine Parks, Australia - Jake R. Lowe; Samuel D. Payet; Hugo B. Harrison; Jean‐Paul A. Hobbs; Andrew S. Hoey; Brett M. Taylor; Tane H. Sinclair‐Taylor; Morgan S. Pratchett (Journal of Fish Biology, 2021)
Environmental temperature is an important determinant of physiological processes and life histories in ectotherms. Over latitudinal scales, variation in temperature has been linked to changes in life‐history traits and demographic rates, with growth and mortality rates generally being greatest at low latitudes, and longevity and maximum length being greater at higher latitudes. Using the two‐spined angelfish, Centropyge bispinosa , as our focal species, we compared growth patterns, growth rates, longevity, mortality, asymptotic length and maximum length across 22 reefs that span 13° of latitude within the Great Barrier Reef Marine Park (GBRMP) and the Coral Sea Marine Park (CSMP), Australia. We found no predictable latitudinal variation in mortality rates, growth patterns, growth rates, asymptotic or maximum length of C. bispinosa at regional to biogeographic scales. However, C. bispinosa consistently exhibited reduced longevity at lower, warmer latitudes within the CSMP. The greatest differences in mean maximum length of C. bispinosa were between continental (GBRMP) and oceanic (central CSMP) reefs of similar latitude, with individuals being larger on average on continental versus oceanic reefs. The lack of predictable life‐history and demographic variation in C. bispinosa across a 13° latitudinal gradient within the CSMP, coupled with differences in mean maximum length between continental and oceanic reefs at similar latitudes, suggest that local environmental conditions have a greater influence than environmental temperature on the demographic rates and life‐history traits of C. bispinosa .

Non-random Co-occurrence of Juvenile White Sharks (Carcharodon carcharias) at Seasonal Aggregation Sites in Southern California - James M. Anderson; Alyssa J. Clevenstine; Brian S. Stirling; Echelle S. Burns; Emily N. Meese; Connor F. White; Ryan K. Logan; John O’Sullivan; Patrick T. Rex; Jack May; Kady Lyons; Chuck Winkler; et al. (Frontiers in Marine Science, 2021)
Many terrestrial and aquatic taxa are known to form periodic aggregations, whether across life history or solely during specific life stages, that are generally governed by the availability and distribution of resources. Associations between individuals during such aggregation events are considered random and not driven by social attraction or underlying community structure. White sharks ( Carcharodon carcharias ) have been described as a species that exhibits resource-driven aggregative behaviors across ontogenetic stages and juvenile white sharks are known to form aggregations at specific nursery sites where individuals may remain for extended periods of time in the presence of other individuals. We hypothesized juvenile white sharks form distinct communities during these critical early phases of ontogeny and discuss how a tendency to co-occur across life stages may be seeded by the formation of these communities in early ontogeny. We present results from a series of social network analyses of 86 juvenile white sharks derived from 6 years of passive acoustic telemetry data in southern California, demonstrating the likelihood of association of tagged juvenile white sharks is greater when sharks are of similar size-classes. Individuals in observed networks exhibited behaviors that best approximated fission-fusion dynamics with spatiotemporally unstable group membership. These results provide evidence of possible non-resource driven co-occurrence and community structure in juvenile white sharks during early life stages.

‘Can homegardens assist in enhancing the domestic food security?’ A study in Jaffna Peninsula, Sri lanka - W. A. M. Lowe; J. Sinniah; K. Jeyavanan; G. L. L. P. Silva; D. K. N. G. Pushpakumara (Agroforestry Systems, 2021)

The 2018–2019 weak El Niño: Predicting the risk of a dengue outbreak in Machala, Ecuador - Desislava Petrova; Xavier Rodó; Rachel Sippy; Joan Ballester; Raul Mejía; Efraín Beltrán‐Ayala; Mercy J. Borbor‐Cordova; G. Mauricio Vallejo; Alfredo J. Olmedo; Anna M. Stewart‐Ibarra; Rachel Lowe (International Journal of Climatology, 2021)
Between October 2018 ‐ May 2019, sea surface temperature conditions in the central‐eastern tropical Pacific indicated a mild El Niño event. In May 2019, the global El Niño Southern Oscillation (ENSO) forecast consensus was that these generally weak warm patterns will persist at least until the end of the northern hemisphere summer. El Niño and its impact on local climatic conditions in southern coastal Ecuador influence the inter‐annual transmission of dengue fever in the region. In this study, we use an ENSO model to issue forecasts of El Niño for the year 2019, which are then used to predict local climate variables, precipitation and minimum temperature, in the city of Machala, Ecuador. All these forecasts are incorporated in a dengue transmission model, specifically developed and tested for this area, to produce out‐of‐sample predictions of dengue risk. Predictions are issued at the beginning of January 2019 for the whole year, thus providing the longest forecast lead time of 12 months. Preliminary results indicate that the mild and ongoing El Niño event did not provide the optimum climate conditions for dengue transmission, with the model predicting a very low probability of a dengue outbreak during the typical peak season in Machala in 2019. This is contrary to 2016, when a large El Niño event resulted in excess rainfall and warmer temperatures in the region, and a dengue outbreak occurred 3 months earlier than expected. This event was successfully predicted using a similar prediction framework to the one applied here. With the present study, we continue our efforts to build and test a climate service tool to issue early warnings of dengue outbreaks in the region.

Future changes to high impact weather in the UK - Helen M. Hanlon; Dan Bernie; Giulia Carigi; Jason A. Lowe (Climatic Change, 2021)
High impact weather events such as extreme temperatures or rainfall can cause significant disruption across the UK affecting sectors such as health, transport, agriculture and energy. In this study we draw on the latest set of UK climate projections, UKCP, to examine metrics relating to high-impact weather over the UK and how these change with different levels of future global warming from 1.5 °C to 4 °C above pre-industrial. The changes to these hazards show increases in the frequency of extremely hot days and nights, with a UK average increase in hot days of between 5 and 39 days per year between 1.5 °C and 4 °C of global warming. Projections indicate an increase in cooling degree days of 134–627% and an increase in growing degree days of 19–60% between 1.5 °C and 4 °C of global warming. Extremely hot nights, which are currently rare, are emerging as more common occurrences. The frequency of high daily temperatures and rainfall increase systematically, while the frequency of very cold conditions (based on days where temperatures fall below 0 °C) is shown to decrease by 10 to 49 days per year. A reduction in heating degree days, of 11–32% between 1.5 °C and 4 °C of warming, is projected. Levels of daily rainfall, which currently relate to increased risk of river flooding, are shown to increase across the country, with increases of days with high impact levels of rainfall occurring by 1 to 8 days per year between 1.5 °C and 4 °C of warming. Average drought severity is projected to increase for 3-, 6-, 12- and 36-month-long droughts. The largest changes in the severity of the 12-month drought are between −3 and +19% between 1.5 °C and 4 °C of warming and for 36-month drought between −2 and +54% between 1.5 °C and 4 °C of warming. The projected future changes in high impact weather from this study will enable the characterization of climate risks and ultimately be able to better inform adaptation planning in different sectors to support the increase in resilience of the UK to future climate variability and change.

Current carbon prices do not stack up to much land use change, despite bundled ecosystem service co‐benefits - David M. Summers; Courtney M. Regan; Claire Settre; Jeffery D. Connor; Patrick O’Connor; Hayley Abbott; Jacqueline Frizenschaf; Leon van der Linden; Andrew Lowe; Katja Hogendoorn; Scott Groom; Timothy R. Cavagnaro (Global Change Biology, 2021)
Biological sources of carbon sequestration such as revegetation have been highlighted as important avenues to combat climate change and meet global targets by the global community including the Paris Climate Agreement. However, current and projected carbon prices present a considerable barrier to broad‐scale adoption of tree planting as a key mitigation strategy. One avenue to provide additional economic and environmental incentives to encourage wider adoption of revegetation is the bundling or stacking of additional co‐beneficial ecosystem services that can be realized from tree planting. Using the World's largest land‐based carbon credit trading scheme, the Australian Emissions Reduction Scheme (ERF), we examine the potential for three pairs of ecosystem services, where the carbon sequestration value of land use change is paired with an additional co‐benefit with strong prospects for local tangible benefits to land owners/providers. Two cases consider agricultural provisioning values that can be realized by the landowners in higher returns: increased pollination services and reduced lamb mortality. The third case examined payments for tree plantings along riparian buffers, with payments to farmers by a water utility who realizes the benefit from reduced treatment cost due to water quality improvements. Economic incentives from these co‐benefit case studies were found to be mixed, with avoided treatment costs from water quality paired with carbon payments the most promising, while pollination and reduced lamb mortality paired with carbon payments were unable to bridge the economic gap except under the most optimistic assumptions. We conclude that the economics case for significant land use change are likely to be geographically dispersed and only viable in relatively niche landscape positions in high establishment, high opportunity cost areas even when carbon payments are augmented with the value of co‐benefits classified as providing direct and local benefits.

Interannual Nearshore Habitat Use of Young of the Year White Sharks Off Southern California - James M. Anderson; Echelle S. Burns; Emily N. Meese; Thomas J. Farrugia; Brian S. Stirling; Connor F. White; Ryan K. Logan; John O’Sullivan; Chuck Winkler; Christopher G. Lowe (Frontiers in Marine Science, 2021)
Young-of-the-year (YOY) and juvenile-stage white sharks may use southern California nearshore beach habitats more extensively than previously known, within meters of some of the most heavily used beaches in the world. Such knowledge forms a critical component of species management and conservation plans, in addition to public safety and risk mitigation planning. We used data derived from a combination of satellite tag locations (13 animals over 3 years) and passive acoustic monitoring (34 animals over 8 years) to examine the occurrence, relative abundance, and residency patterns of YOY white sharks in southern California waters. Our results suggest that southern California contains spatiotemporally dynamic centers of primary nursery habitat. Tagged YOY white sharks formed loose aggregations at “hotspot” locations that were interannually variable, where individuals exhibited temporal fidelity, higher levels of residency, and spatially restricted movements, with multiple YOY individuals simultaneously displaying this behavior. While models of biotic and abiotic variables suggested relative abundance of tagged sharks may be predicted by sea surface temperature, salinity and productivity (chlorophyll-A), these predictors were not consistent across all years of the study. Thus, novel approaches that incorporate technologies to derive high resolution environmental data, paired with more comprehensive telemetry datasets are therefore required to better understand the extrinsic factors that drive habitat selection and residency patterns in juvenile white sharks.

Environmental disturbance events drive declines in juvenile wrasse biomass on inshore coral reefs of the Great Barrier Reef - J. R. Lowe; D. H. Williamson; D. M. Ceccarelli; R. D. Evans; G. R. Russ (Environmental Biology of Fishes, 2020)

Spectral Wave-Driven Bedload Transport Across a Coral Reef Flat/Lagoon Complex - Kurt J. Rosenberger; Curt D. Storlazzi; Olivia M. Cheriton; Andrew W. M. Pomeroy; Jeff E. Hansen; Ryan J. Lowe; Mark L. Buckley (Frontiers in Marine Science, 2020)

Comparative demography of commercially important species of coral grouper, Plectropomus leopardus and P. laevis , from Australia's great barrier reef and Coral Sea marine parks - Samuel D. Payet; Jake R. Lowe; Bruce D. Mapstone; Morgan S. Pratchett; Tane H. Sinclair‐Taylor; Brett M. Taylor; Peter A. Waldie; Hugo B. Harrison (Journal of Fish Biology, 2020)
Understanding the spatial and environmental variation in demographic processes of fisheries target species, such as coral grouper (Genus: Plectropomus ), is important for establishing effective management and conservation strategies. Herein we compare the demography of Plectropomus leopardus and P. laevis between Australia's Great Barrier Reef Marine Park (GBRMP), which has been subject to sustained and extensive fishing pressure, and the oceanic atolls of Australia's Coral Sea Marine Park (CSMP), where there is very limited fishing for reef fishes. Coral grouper length‐at‐age data from contemporary and historical otolith collections across 9.4 degrees of latitude showed little difference in lifetime growth between GBRMP and CSMP regions. Plectropomus laevis populations in GBRMP reefs had significantly higher rates of total mortality than populations in the CSMP. Mean maximum lengths and mean maximum ages of P. laevis were also smaller in the GBRMP than in the CSMP, even when considering populations sampled within GBRMP no‐take marine reserves (NTMRs). Plectropomus leopardus , individuals were on average smaller on fished reefs than NTMRs in the GBRMP, but all other aspects of demography were broadly similar between regions despite the negligible levels of fishing pressure in the CSMP. Similarities between regions in growth profiles and length‐at‐age comparisons of P. laevis and P. leopardus suggest that the environmental differences between the CSMP and the GBRMP may not have significant impacts on lifetime growth. Our results show that fishing may have influenced the demography of coral grouper on the GBR, particularly for the slower growing and longer lived species, P. laevis .

A set of 156 SNP markers for teak (Tectona grandis Linn. f.) - Bianca Dunker; Eleanor E. Dormontt; Kor-jent van Dijk; Rainbo R. M. Dixon; Duncan I. Jardine; Dona Kireta; I. L. G. Nurtjahjaningsih; Thwe Thwe Win; Anto Rimbawanto; Andrew J. Lowe (Conservation Genetics Resources, 2020)

Maternal cannibalism in two populations of wild chimpanzees - Pawel Fedurek; Patrick Tkaczynski; Caroline Asiimwe; Catherine Hobaiter; Liran Samuni; Adriana E. Lowe; Appolinaire Gnahe Dijrian; Klaus Zuberbühler; Roman M. Wittig; Catherine Crockford (Primates, 2020)
Maternal cannibalism has been reported in several animal taxa, prompting speculations that the behavior may be part of an evolved strategy. In chimpanzees, however, maternal cannibalism has been conspicuously absent, despite high levels of infant mortality and reports of non-maternal cannibalism. The typical response of chimpanzee mothers is to abandon their deceased infant, sometimes after prolonged periods of carrying and grooming the corpse. Here, we report two anomalous observations of maternal cannibalism in communities of wild chimpanzees in Uganda and Ivory Coast and discuss the evolutionary implications. Both infants likely died under different circumstances; one apparently as a result of premature birth, the other possibly as a result of infanticide. In both cases, the mothers consumed parts of the corpse and participated in meat sharing with other group members. Neither female presented any apparent signs of ill health before or after the events. We concluded that, in both cases, cannibalizing the infant was unlikely due to health-related issues by the mothers. We discuss these observations against a background of chimpanzee mothers consistently refraining from maternal cannibalism, despite ample opportunities and nutritional advantages. We conclude that maternal cannibalism is extremely rare in this primate, likely due to early and strong mother–offspring bond formation, which may have been profoundly disrupted in the current cases.

Rainfall threshold for initiating effective stress decrease and failure in weathered tephra slopes - Max Oke Kluger; M. Ehsan Jorat; Vicki G. Moon; Stefan Kreiter; Willem P. de Lange; Tobias Mörz; Thomas Robertson; David J. Lowe (Landslides, 2020)

Asymmetry in Herbivore Effector Responses: Caterpillar Frass Effectors Reduce Performance of a Subsequent Herbivore - Swayamjit Ray; Anjel M. Helms; Nina L. Matulis; Elizabeth Davidson-Lowe; William Grisales; Jared G. Ali (Journal of Chemical Ecology, 2020)

Geophysical and archaeological investigations of Baker’s Flat, a nineteenth century historic Irish site in South Australia - Kelsey M. Lowe; Susan Arthure; Lynley A. Wallis; Josh Feinberg (Archaeological and Anthropological Sciences, 2020)

Crossing new frontiers: extending tephrochronology as a global geoscientific research tool - Peter M. Abbott; Britta J. L. Jensen; David J. Lowe; Takehiko Suzuki; Daniel Veres (Journal of Quaternary Science, 2020)

Correction to: Concepts and Terminology for Sea Level: Mean, Variability and Change, Both Local and Global - Jonathan M. Gregory; Stephen M. Griffies; Chris W. Hughes; Jason A. Lowe; John A. Church; Ichiro Fukumori; Natalya Gomez; Robert E. Kopp; Felix Landerer; Gonéri Le Cozannet; Rui M. Ponte; Detlef Stammer; et al. (Surveys in Geophysics, 2019)

Concepts and Terminology for Sea Level: Mean, Variability and Change, Both Local and Global - Jonathan M. Gregory; Stephen M. Griffies; Chris W. Hughes; Jason A. Lowe; John A. Church; Ichiro Fukimori; Natalya Gomez; Robert E. Kopp; Felix Landerer; Gonéri Le Cozannet; Rui M. Ponte; Detlef Stammer; et al. (Surveys in Geophysics, 2019)

Responses of coral reef wrasse assemblages to disturbance and marine reserve protection on the Great Barrier Reef - J. R. Lowe; D. H. Williamson; D. M. Ceccarelli; R. D. Evans; G. R. Russ (Marine Biology, 2019)

Antidiabetic, cytotoxic and antioxidant activities of oil extracted from Acrocomia aculeata pulp - Perla V. B. da Silva; Marianne M. Ramiro; Edna K. K. Iriguchi; William A. Corrêa; Jennifer Lowe; Claudia A. L. Cardoso; Arielle C. Arena; Cândida A. L. Kassuya; Rozanna M. Muzzi (Natural Product Research, 2019)

Adapting to change in inland fisheries: analysis from Lake Tanganyika, East Africa - Benjamin S. Lowe; Susan K. Jacobson; Happiness Anold; Athanasio S. Mbonde; Catherine M. O’Reilly (Regional Environmental Change, 2019)

Spatial capture–recapture reveals age- and sex-specific survival and movement in stream amphibians - R. Ken Honeycutt; Justin M. Garwood; Winsor H. Lowe; Blake R. Hossack (Oecologia, 2019)

Future Research Directions on the “Elusive” White Shark - Charlie Huveneers; Kirin Apps; Edgar E. Becerril-García; Barry Bruce; Paul A. Butcher; Aaron B. Carlisle; Taylor K. Chapple; Heather M. Christiansen; Geremy Cliff; Tobey H. Curtis; Toby S. Daly-Engel; Heidi Dewar; et al. (Frontiers in Marine Science, 2018)

Archaeological geophysical survey of a Prehistoric Bronze Age site in Cyprus (Alambra Mouttes)—applications and limitations - Kelsey M. Lowe; Aaron S. Fogel; Andrew Sneddon (Archaeological and Anthropological Sciences, 2018)

Seeds in motion: Genetic assignment and hydrodynamic models demonstrate concordant patterns of seagrass dispersal - Elizabeth A. Sinclair; Leonardo Ruiz‐Montoya; Siegfried L. Krauss; Janet M. Anthony; Renae K. Hovey; Ryan J. Lowe; Gary A. Kendrick (Molecular Ecology, 2018)
Movement is fundamental to the ecology and evolutionary dynamics within species. Understanding movement through seed dispersal in the marine environment can be difficult due to the high spatial and temporal variability of ocean currents. We employed a mutually enriching approach of population genetic assignment procedures and dispersal predictions from a hydrodynamic model to overcome this difficulty and quantify the movement of dispersing floating fruit of the temperate seagrass Posidonia australis Hook.f. across coastal waters in south‐western Australia. Dispersing fruit cohorts were collected from the water surface over two consecutive years, and seeds were genotyped using microsatellite DNA markers. Likelihood‐based genetic assignment tests were used to infer the meadow of origin for seed cohorts and individuals. A three‐dimensional hydrodynamic model was coupled with a particle transport model to simulate the movement of fruit at the water surface. Floating fruit cohorts were mainly assigned genetically to the nearest meadow, but significant genetic differentiation between cohort and most likely meadow of origin suggested a mixed origin. This was confirmed by genetic assignment of individual seeds from the same cohort to multiple meadows. The hydrodynamic model predicted 60% of fruit dispersed within 20 km, but that fruit was physically capable of dispersing beyond the study region. Concordance between these two independent measures of dispersal provides insight into the role of physical transport for long distance dispersal of fruit and the consequences for spatial genetic structuring of seagrass meadows.

Warning signal plasticity in hibiscus harlequin bugs - S. A. Fabricant; E. R. Burdfield-Steel; K. Umbers; E. C. Lowe; M. E. Herberstein (Evolutionary Ecology, 2018)

Comparing depth and seabed terrain preferences of individually identified female humpback whales ( Megaptera novaeangliae ), with and without calf, off Maui, Hawaii - Adam A. Pack; Louis M. Herman; Alison S. Craig; Scott S. Spitz; James O. Waterman; Elia Y. K. Herman; Mark H. Deakos; Siri Hakala; Carley Lowe (Marine Mammal Science, 2018)

Metabolomics of tomato xylem sap during bacterial wilt reveals Ralstonia solanacearum produces abundant putrescine, a metabolite that accelerates wilt disease - Tiffany M. Lowe‐Power; Connor G. Hendrich; Edda von Roepenack‐Lahaye; Bin Li; Dousheng Wu; Raka Mitra; Beth L. Dalsing; Patrizia Ricca; Jacinth Naidoo; David Cook; Amy Jancewicz; Patrick Masson; et al. (Environmental Microbiology, 2018)
Summary Ralstonia solanacearum thrives in plant xylem vessels and causes bacterial wilt disease despite the low nutrient content of xylem sap. We found that R. solanacearum manipulates its host to increase nutrients in tomato xylem sap, enabling it to grow better in sap from infected plants than in sap from healthy plants. Untargeted GC/MS metabolomics identified 22 metabolites enriched in R. solanacearum ‐infected sap. Eight of these could serve as sole carbon or nitrogen sources for R. solanacearum . Putrescine, a polyamine that is not a sole carbon or nitrogen source for R. solanacearum , was enriched 76‐fold to 37 µM in R. solanacearum ‐infected sap. R. solanacearum synthesized putrescine via a SpeC ornithine decarboxylase. A Δ speC mutant required ≥ 15 µM exogenous putrescine to grow and could not grow alone in xylem even when plants were treated with putrescine. However, co‐inoculation with wildtype rescued ΔspeC growth, indicating R. solanacearum produced and exported putrescine to xylem sap. Intriguingly, treating plants with putrescine before inoculation accelerated wilt symptom development and R. solanacearum growth and systemic spread. Xylem putrescine concentration was unchanged in putrescine‐treated plants, so the exogenous putrescine likely accelerated disease indirectly by affecting host physiology. These results indicate that putrescine is a pathogen‐produced virulence metabolite.

Environmental drivers of spider community composition at multiple scales along an urban gradient - E. C. Lowe; C. G. Threlfall; S. M. Wilder; D. F. Hochuli (Biodiversity and Conservation, 2018)

A multi-proxy study of anthropogenic sedimentation and human occupation of Gledswood Shelter 1: exploring an interior sandstone rockshelter in Northern Australia - Kelsey M. Lowe; Susan M. Mentzer; Lynley A. Wallis; James Shulmeister (Archaeological and Anthropological Sciences, 2018)

Dynamics of direct inter-pack encounters in endangered African wild dogs - Neil R Jordan; Christopher Buse; Alan M Wilson; Krystyna A Golabek; Peter J Apps; John C Lowe; Leanne K Van der Weyde; J Weldon McNutt (Behavioral Ecology and Sociobiology, 2017)

Persistence and survival of the spider Nephila plumipes in cities: do increased prey resources drive the success of an urban exploiter? - E. C. Lowe; S. M. Wilder; D. F. Hochuli (Urban Ecosystems, 2016)

Development of SNP markers for Ayous (Triplochiton scleroxylon K. Schum) an economically important tree species from tropical West and Central Africa - D. I. Jardine; C. Blanc-Jolivet; R. R. M. Dixon; E. E. Dormontt; B. Dunker; J. Gerlach; B. Kersten; K.-J. van Dijk; B. Degen; A. J. Lowe (Conservation Genetics Resources, 2016)

No increased risk of acute kidney injury after a single dose of gentamicin in patients with sepsis - Maarten Cobussen; Jaclyn M. L. de Kort; Robert M. Dennert; Selwyn H. Lowe; Patricia M. Stassen (Infectious Diseases, 2016)

Interactions between Bacteria And Aspen Defense Chemicals at the Phyllosphere – Herbivore Interface - Charles J. Mason; Tiffany M. Lowe-Power; Kennedy F. Rubert-Nason; Richard L. Lindroth; Kenneth F. Raffa (Journal of Chemical Ecology, 2016)

Effect of Zinc Intake on Growth in Infants: A Meta-analysis - M. Nissensohn; A. Sánchez-Villegas; D. Fuentes Lugo; P. Henríquez Sánchez; J. Doreste Alonso; L. Peña Quintana; C. Ruano; N. L. Lowe; V. Hall Moran; A. L. Skinner; M. Warthon-Medina; L. Serra-Majem (Critical Reviews in Food Science and Nutrition, 2016)

The impacts of climate change across the globe: A multi-sectoral assessment - N. W. Arnell; S. Brown; S. N. Gosling; P. Gottschalk; J. Hinkel; C. Huntingford; B. Lloyd-Hughes; J. A. Lowe; R. J. Nicholls; T. J. Osborn; T. M. Osborne; G. A. Rose; et al. (Climatic Change, 2016)

Islands in the stream: kelp detritus as faunal magnets - D. O. Duggins; M. C. Gómez-Buckley; R. M. Buckley; A. T. Lowe; A. W. E. Galloway; M. N. Dethier (Marine Biology, 2016)

Resilience of coral calcification to extreme temperature variations in the Kimberley region, northwest Australia - S. S. Dandan; J. L. Falter; R. J. Lowe; M. T. McCulloch (Coral Reefs, 2015)

A population PK model for citalopram and its major metabolite, N-desmethyl citalopram, in rats - Nieves Velez de Mendizabal; Kimberley Jackson; Brian Eastwood; Steven Swanson; David M. Bender; Stephen Lowe; Robert R. Bies (Journal of Pharmacokinetics and Pharmacodynamics, 2015)

A set of 204 SNP and INDEL markers for Bigleaf maple (Acer macrophyllum Pursch) - D. I. Jardine; E. E. Dormontt; K.-J. van Dijk; R. R. M. Dixon; B. Dunker; A. J. Lowe (Conservation Genetics Resources, 2015)

Pollen–climate reconstruction from northern South Island, New Zealand (41°S), reveals varying high‐ and low‐latitude teleconnections over the last 16 000 years - Ignacio A. Jara; Rewi M. Newnham; Marcus J. Vandergoes; Courtney R. Foster; David J. Lowe; Janet M. Wilmshurst; Patricio I. Moreno; James A. Renwick; Aline M. Homes (Journal of Quaternary Science, 2015)
We present a 16 000‐year vegetation and climate reconstruction from pollen and plant macrofossil records obtained at a small alpine lake in South Island, New Zealand (41°S). The expansion of lowland forest taxa suggests a lifting of the altitudinal forest limits because of a warming pulse between 13 and 10k cal a BP and between 7 and 6k cal a BP, while their decline relative to upland forest taxa indicates cooling phases between 10 and 7k cal a BP and over the last 3000 years. The modern treeline was first established locally by 9.7k cal a BP. Forest persisted at the site until 3k cal a BP then disappeared from the record. Close correspondence between the temperature trends inferred from the pollen and macrofossil records and proxies from Antarctica and the Southern Ocean suggests a strong teleconnection between New Zealand and the Southern Hemisphere high‐latitudes between 15 and 6k cal a BP. We note that the breakdown of this coupling, a cooling trend in Adelaide Tarn and the local disappearance of beech forest after 3k cal a BP occur during a period of increased frequency of El Niño events, suggesting an enhanced teleconnection with the low‐latitudes during the late Holocene.

Influence of putative forest refugia and biogeographic barriers on the level and distribution of genetic variation in an African savannah tree, Khaya senegalensis (Desr.) A. Juss - Gary J. Sexton; C. H. Frere; A. Kalinganire; A. Uwamariya; A. J. Lowe; I. D. Godwin; P. J. Prentis; M. J. Dieters (Tree Genetics & Genomes, 2015)

Environmental DNA particle size distribution from Brook Trout (Salvelinus fontinalis) - Taylor M. Wilcox; Kevin S. McKelvey; Michael K. Young; Winsor H. Lowe; Michael K. Schwartz (Conservation Genetics Resources, 2015)

Model structure in observational constraints on transient climate response - Richard J. Millar; Alexander Otto; Piers M. Forster; Jason A. Lowe; William J. Ingram; Myles R. Allen (Climatic Change, 2015)

Insights into the life history and ecology of a large shortfin mako shark Isurus oxyrinchus captured in southern California - K. Lyons; A. Preti; D. J. Madigan; R. J. D. Wells; M. E. Blasius; O. E. Snodgrass; D. Kacev; J. D. Harris; H. Dewar; S. Kohin; K. MacKenzie; C. G. Lowe (Journal of Fish Biology, 2015)
In June 2013, a record‐breaking female Isurus oxyrinchus (total length 373 cm, mass 600 kg) was captured by rod and reel off Huntington Beach, California, where it was subsequently donated to research and provided a rare opportunity to collect the first data for a female I. oxyrinchus of this size. Counts of vertebral band pairs estimate the shark to have been c. 22 years old, depending upon assumptions of band‐pair deposition rates, and the distended uteri and spent ovaries indicated that this shark had recently given birth. The stomach contained a c. 4 year‐old female California sea lion Zalophus californianus that confirmed the high trophic position of this large I. oxyrinchus , which was corroborated with the high levels of measured contaminants and tissue isotope analyses.

Tiered Approaches to Chromatographic Bioanalytical Method Performance Evaluation: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Team - S. Lowes; R. Hucker; M. Jemal; J. C. Marini; V. M. Rezende; R. Shoup; P. Singhal; P. Timmerman; T. Yoneyama; N. Weng; D. Zimmer (The AAPS Journal, 2015)

Transient climate changes in a perturbed parameter ensemble of emissions-driven earth system model simulations - James M. Murphy; Ben B. B. Booth; Chris A. Boulton; Robin T. Clark; Glen R. Harris; Jason A. Lowe; David M. H. Sexton (Climate Dynamics, 2014)

Using palaeoenvironmental DNA to reconstruct past environments: progress and prospects - NICOLAS J. RAWLENCE; DAVID J. LOWE; JAMIE R. WOOD; JENNIFER M. YOUNG; G. JOCK CHURCHMAN; YU‐TUAN HUANG; ALAN COOPER (Journal of Quaternary Science, 2014)
Palaeoenvironmental DNA (PalEnDNA) is defined as ancient DNA (aDNA) originating from disseminated genetic material within palaeoenvironmental samples. Sources of PalEnDNA include marine and lake sediments, peat, loess, till, ice, permafrost, palaeosols, coprolites, preserved gut contents, dental calculus, tephras, and soils as well as deposits in caves/rockshelters and at archaeological sites. PalEnDNA analysis provides a relatively new tool for Quaternary and archaeological sciences and its applications have included palaeoenvironmental and palaeodietary reconstructions, testing hypotheses regarding megafaunal extinctions, human–environment interactions, taxonomic studies, and studies of DNA damage. Because PalEnDNA samples comprise markedly different materials, and represent wide‐ranging depositional and taphonomic contexts, various issues must be addressed to achieve robust, reproducible findings. Such issues include climatic and temporal limitations, the biological origin and state (free versus bound) of PalEnDNA, stratigraphic reliability, sterile sampling, ability to distinguish modern from aDNA signals, DNA damage and PCR amplification, DNA extraction methods, and taxonomic resolution. In this review, we provide a non‐specialist introduction to the use of PalEnDNA for Quaternary and archaeological researchers, assess attributes and limitations of this palaeoenvironmental tool, and discuss future prospects of using PalEnDNA to reconstruct past environments.

Partitioning the non-consumptive effects of predators on prey with complex life histories - Jon M. Davenport; Blake R. Hossack; Winsor H. Lowe (Oecologia, 2014)

Contrasting levels of connectivity and localised persistence characterise the latitudinal distribution of a wind-dispersed rainforest canopy tree - Margaret M. Heslewood; Andrew J. Lowe; Darren M. Crayn; Maurizio Rossetto (Genetica, 2014)

A blocking primer increases specificity in environmental DNA detection of bull trout (Salvelinus confluentus) - Taylor M. Wilcox; Michael K. Schwartz; Kevin S. McKelvey; Michael K. Young; Winsor H. Lowe (Conservation Genetics Resources, 2014)

Snapper ( Chrysophrys auratus ): a review of life history and key vulnerabilities in New Zealand - DM Parsons; CJ Sim‐Smith; M Cryer; MP Francis; B Hartill; EG Jones; A Le Port; M Lowe; J McKenzie; M Morrison; LJ Paul; C Radford; et al. (New Zealand Journal of Marine and Freshwater Research, 2014)
Snapper ( Chrysophrys auratus ) is an important coastal fish species in New Zealand for a variety of reasons, but the large amount of research conducted on snapper has not been reviewed. Here, we review life history information and potential threats for snapper in New Zealand. We present information on snapper life history, defining stages (eggs and larvae, juvenile and adult), and assess potential threats and knowledge gaps. Overall we identify six key points: 1. post‐settlement snapper are highly associated with certain estuarine habitats that are under threat from land‐based stressors. This may serve as a bottleneck for snapper populations; 2. the largest knowledge gaps relate to the eggs and larvae. Additional knowledge may help to anticipate the effects of climate change, which will likely have the greatest influence on these early life stages; 3. ocean acidification, from land‐based sources and from climate change, may be an important threat to larval snapper; 4. a greater understanding of population connectivity would improve certainty around the sustainability of fishery exploitation; 5. the collateral effects of fishing are likely to be relevant to fishery productivity, ecosystem integrity and enduser value; 6. our understanding of the interrelationships between snapper and other ecosystem components is still deficient.

Genomic evidence for the parallel evolution of coastal forms in the Senecio lautus complex - Federico Roda; Luke Ambrose; Gregory M. Walter; Huanle L. Liu; Andrea Schaul; Andrew Lowe; Pieter B. Pelser; Peter Prentis; Loren H. Rieseberg; Daniel Ortiz‐Barrientos (Molecular Ecology, 2013)
Instances of parallel ecotypic divergence where adaptation to similar conditions repeatedly cause similar phenotypic changes in closely related organisms are useful for studying the role of ecological selection in speciation. Here we used a combination of traditional and next generation genotyping techniques to test for the parallel divergence of plants from the S enecio lautus complex, a phenotypically variable groundsel that has adapted to disparate environments in the South Pacific. Phylogenetic analysis of a broad selection of S enecio species showed that members of the S . lautus complex form a distinct lineage that has diversified recently in Australasia. An inspection of thousands of polymorphisms in the genome of 27 natural populations from the S . lautus complex in Australia revealed a signal of strong genetic structure independent of habitat and phenotype. Additionally, genetic differentiation between populations was correlated with the geographical distance separating them, and the genetic diversity of populations strongly depended on geographical location. Importantly, coastal forms appeared in several independent phylogenetic clades, a pattern that is consistent with the parallel evolution of these forms. Analyses of the patterns of genomic differentiation between populations further revealed that adjacent populations displayed greater genomic heterogeneity than allopatric populations and are differentiated according to variation in soil composition. These results are consistent with a process of parallel ecotypic divergence in face of gene flow.

RAD‐Seq derived markers flank the shell colour and banding loci of the Cepaea nemoralis supergene - Paul M. Richards; M. Maureen Liu; Natalie Lowe; John W. Davey; Mark L. Blaxter; Angus Davison (Molecular Ecology, 2013)
Studies on the classic shell colour and banding polymorphism of the land snail C epaea played a crucial role in establishing the importance of natural selection in maintaining morphological variation. Cepaea is also a pre‐eminent model for ecological genetics because the outward colour and banding phenotype is entirely genetically determined, primarily by a ‘supergene’ of at least five loci. Unfortunately, progress in understanding the evolution and maintenance of the C epaea polymorphism stalled, partly because of a lack of genetic markers. With a view to re‐establish C epaea as a prominent model of molecular ecology, we made six laboratory crosses of C epaea nemoralis , five of which segregated for shell ground colour ( C ) and the presence or absence of bands ( B ). First, scoring of colour and banding in 323 individuals found no recombination between the C and B loci of the supergene. Second, using restriction site–associated DNA sequencing ( RAD ‐ S eq) of two parents and 22 offspring, we identified 44 anonymous markers putatively linked to the colour ( C ) and banding ( B ) loci. The genotype of eleven of the most promising RAD ‐ S eq markers was independently validated in the same 22 offspring, then up to a further 146 offspring were genotyped. The closest RAD ‐ S eq markers scored are within ~0.6 centimorgan (cM) of the C ‐ B supergene linkage group, with the combined loci together forming a 35.8 cM linkage map of markers that flank both sides of the C epaea C ‐ B supergene.

Macroparasites at peripheral sites of infection are major and dynamic modifiers of systemic antimicrobial pattern recognition responses - I. M. Friberg; S. Little; C. Ralli; A. Lowe; A. Hall; J. A. Jackson; J. E. Bradley (Molecular Ecology, 2013)
Immune defences and the maintenance of immunological homeostasis in the face of pathogenic and commensal microbial exposures are channelled by innate antimicrobial pattern recognition receptors ( PRR s) such as toll‐like receptors ( TLR s). Whilst PRR ‐mediated response programmes are the result of long‐term host‐pathogen or host–commensal co‐evolutionary dynamics involving microbes, an additional possibility is that macroparasitic co‐infections may be a significant modifier of such interactions. We demonstrate experimentally that macroparasites (the model gastrointestinal nematode, H eligmosomoides ) at peripheral sites of infection cause substantial alteration of the expression and function of TLR s at a systemic level (in cultured splenocytes), predominantly up‐regulating TLR 2, TLR 4 and TLR 9‐mediated cytokine responses at times of high standing worm burdens. We consistently observed such effects in BALB /c and C57 BL /6 mice under single‐pulse and trickle exposures to H eligmosomoides larvae and in SWR and CBA mice under single‐pulse exposures. A complementary long‐term survey of TLR 2‐mediated tumour necrosis factor‐alpha responses in wild wood mice ( A podemus sylvaticus ) was consistent with substantial effects of macroparasites under some environmental conditions. A general pattern, though, was for the associations of macroparasites with TLR function to be temporally dynamic and context‐dependent: varying with different conditions of infection exposure in the field and laboratory and with host genetic strain in the laboratory. These results are compelling evidence that macroparasites are a major and dynamic modifier of systemic innate antimicrobial responsiveness in naturally occurring mammals and thus likely to be an important influence on the interaction between microbial exposures and the immune system.

Which provenance and where? Seed sourcing strategies for revegetation in a changing environment - Martin F. Breed; Michael G. Stead; Kym M. Ottewell; Michael G. Gardner; Andrew J. Lowe (Conservation Genetics, 2013)

The effects of aggressive mitigation on steric sea level rise and sea ice changes - J. Körper; I. Höschel; J. A. Lowe; C. D. Hewitt; D. Salas y Melia; E. Roeckner; H. Huebener; J.-F. Royer; J.-L. Dufresne; A. Pardaens; M. A. Giorgetta; M. G. Sanderson; et al. (Climate Dynamics, 2013)

Abrupt CO2 experiments as tools for predicting and understanding CMIP5 representative concentration pathway projections - Peter Good; Jonathan M. Gregory; Jason A. Lowe; Timothy Andrews (Climate Dynamics, 2013)

EURRECA—Estimating Zinc Requirements for Deriving Dietary Reference Values - Nicola M. Lowe; Fiona C. Dykes; Anna-Louise Skinner; Sujata Patel; Marisol Warthon-Medina; Tamás Decsi; Katalin Fekete; Olga W. Souverein; Carla Dullemeijer; Adriënne E. Cavelaars; Lluis Serra-Majem; Mariela Nissensohn; et al. (Critical Reviews in Food Science and Nutrition, 2013)

Particulate nutrient fluxes over a fringing coral reef: Source‐sink dynamics inferred from carbon to nitrogen ratios and stable isotopes - Alex S. J. Wyatt; Ryan J. Lowe; Stuart Humphries; Anya M. Waite (Limnology and Oceanography, 2013)
We examined spatial and temporal variations in particulate organic matter (POM) dynamics over a fringing coral reef (Ningaloo Reef) in Western Australia during the austral autumn and spring. Total POM concentrations generally did not differ between seasons or reef zones, but the composition of POM, in terms of carbon isotope ratios ( δ 13 C‐POM), carbon to nitrogen ratios (C : N), and fatty acids, changed consistently in water flowing across the reef. Both δ 13 C‐POM and C : N increased from the fore reef to the reef flat and lagoon, −23.0‰ to −20.1‰ and 7.31 to 8.34, respectively. Average rates of net POM uptake by the reef community were highest over the reef crest (4 to 30 mmol N m −2 d −1 and 6 to 130 mmol C m −2 d −1 ), with a Bayesian isotope model confirming independent measurements of high uptake rates of allochthonous POM (oceanic phyto‐ and zooplankton). In contrast, over the reef flat, net release of POM was observed (−4 to −5 mmol N m −2 d −1 and −50 mmol C m −2 d −1 ), with gross release rates (estimated as −6 to −8 mmol N m −2 d −1 and −30 to −90 mmol C m −2 d −1 ) indicating that the release of autochthonous POM may be of similar magnitude to allochthonous uptake. Examining POM dynamics in terms of gross fluxes reinforces the dependence of coral reef systems on oceanographic processes for allochthonous POM supply, as well as highlighting the potential for autochthonous POM production to supply nutrients to benthic and pelagic communities downstream.

A step-response approach for predicting and understanding non-linear precipitation changes - Peter Good; William Ingram; F. Hugo Lambert; Jason A. Lowe; Jonathan M. Gregory; Mark J. Webb; Mark A. Ringer; Peili Wu (Climate Dynamics, 2012)

Pollen diversity matters: revealing the neglected effect of pollen diversity on fitness in fragmented landscapes - Martin F. Breed; Maria H. K. Marklund; Kym M. Ottewell; Michael G. Gardner; J. Berton C. Harris; Andrew J. Lowe (Molecular Ecology, 2012)
Few studies have documented the impacts of habitat fragmentation on plant mating patterns together with fitness. Yet, these processes require urgent attention to better understand the impact of contemporary landscape change on biodiversity and for guiding native plant genetic resource management. We examined these relationships using the predominantly insect‐pollinated E ucalyptus socialis . Progeny were collected from trees located in three increasingly disturbed landscapes in southern Australia and were planted out in common garden experiments. We show that individual mating patterns were increasingly impacted by lower conspecific density caused by habitat fragmentation. We determined that reduced pollen diversity probably has effects over and above those of inbreeding on progeny fitness. This provides an alternative mechanistic explanation for the indirect density dependence often inferred between conspecific density and offspring fitness.

Formal subdivision of the Holocene Series/Epoch: a Discussion Paper by a Working Group of INTIMATE (Integration of ice‐core, marine and terrestrial records) and the Subcommission on Quaternary Stratigraphy (International Commission on Stratigraphy) - M. J. C. Walker; M. Berkelhammer; S. Björck; L. C. Cwynar; D. A. Fisher; A. J. Long; J. J. Lowe; R. M. Newnham; S. O. Rasmussen; H. Weiss (Journal of Quaternary Science, 2012)
This discussion paper, by a Working Group of INTIMATE (Integration of ice‐core, marine and terrestrial records) and the Subcommision on Quaternary Stratigraphy (SQS) of the International Commission on Stratigraphy (ICS), considers the prospects for a formal subdivision of the Holocene Series/Epoch. Although previous attempts to subdivide the Holocene have proved inconclusive, recent developments in Quaternary stratigraphy, notably the definition of the Pleistocene–Holocene boundary and the emergence of formal subdivisions of the Pleistocene Series/Epoch, mean that it may be timely to revisit this matter. The Quaternary literature reveals a widespread but variable informal usage of a tripartite division of the Holocene (‘early’, ‘middle’ or ‘mid’, and ‘late’), and we argue that this de facto subdivision should now be formalized to ensure consistency in stratigraphic terminology. We propose an Early–Middle Holocene Boundary at 8200 a BP and a Middle–Late Holocene Boundary at 4200 a BP, each of which is linked to a Global Stratotype Section and Point (GSSP). Should the proposal find a broad measure of support from the Quaternary community, a submission will be made to the International Union of Geological Sciences (IUGS), via the SQS and the ICS, for formal ratification of this subdivision of the Holocene Series/Epoch. Copyright © 2012 John Wiley & Sons, Ltd.

ArxA, a new clade of arsenite oxidase within the DMSO reductase family of molybdenum oxidoreductases - Kamrun Zargar; Alison Conrad; David L. Bernick; Todd M. Lowe; Viktor Stolc; Shelley Hoeft; Ronald S. Oremland; John Stolz; Chad W. Saltikov (Environmental Microbiology, 2012)
Summary Arsenotrophy, growth coupled to autotrophic arsenite oxidation or arsenate respiratory reduction, occurs only in the prokaryotic domain of life. The enzymes responsible for arsenotrophy belong to distinct clades within the DMSO reductase family of molybdenum‐containing oxidoreductases: specifically arsenate respiratory reductase, ArrA, and arsenite oxidase, AioA (formerly referred to as AroA and AoxB). A new arsenite oxidase clade, ArxA, represented by the haloalkaliphilic bacterium Alkalilimnicola ehrlichii strain MLHE‐1 was also identified in the photosynthetic purple sulfur bacterium Ectothiorhodospira sp. strain PHS‐1. A draft genome sequence of PHS‐1 was completed and an arx operon similar to MLHE‐1 was identified. Gene expression studies showed that arxA was strongly induced with arsenite. Microbial ecology investigation led to the identification of additional arxA ‐like sequences in Mono Lake and Hot Creek sediments, both arsenic‐rich environments in California. Phylogenetic analyses placed these sequences as distinct members of the ArxA clade of arsenite oxidases. ArxA‐like sequences were also identified in metagenome sequences of several alkaline microbial mat environments of Yellowstone National Park hot springs. These results suggest that ArxA‐type arsenite oxidases appear to be widely distributed in the environment presenting an opportunity for further investigations of the contribution of Arx‐dependent arsenotrophy to the arsenic biogeochemical cycle.

Response to “Comment on ‘Otolith Microchemistry Reveals Substantial Use of Freshwater by Southern Flounder in the Northern Gulf of Mexico’” by Pedro Morais - Michael R. Lowe; Stuart A. Ludsin; Brian J. Fryer; Russell A. Wright; Dennis R. DeVries; Troy M. Farmer (Estuaries and Coasts, 2012)

Estrogen-related genes and their contribution to racial differences in breast cancer risk - Kerryn W. Reding; Chu Chen; Kimberly Lowe; David R. Doody; Christopher S. Carlson; Christina T. Chen; John Houck; Linda K. Weiss; Polly A. Marchbanks; Leslie Bernstein; Robert Spirtas; Jill A. McDonald; et al. (Cancer Causes & Control, 2012)

Shifts in reproductive assurance strategies and inbreeding costs associated with habitat fragmentation in Central American mahogany - Martin F. Breed; Michael G. Gardner; Kym M. Ottewell; Carlos M. Navarro; Andrew J. Lowe (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 444–452 Abstract The influence of habitat fragmentation on mating patterns and progeny fitness in trees is critical for understanding the long‐term impact of contemporary landscape change on the sustainability of biodiversity. We examined the relationship between mating patterns, using microsatellites, and fitness of progeny, in a common garden trial, for the insect‐pollinated big‐leaf mahogany, Swietenia macrophylla King, sourced from forests and isolated trees in 16 populations across Central America. As expected, isolated trees had disrupted mating patterns and reduced fitness. However, for dry provenances, fitness was negatively related to correlated paternity, while for mesic provenances, fitness was correlated positively with outcrossing rate and negatively with correlated paternity. Poorer performance of mesic provenances is likely because of reduced effective pollen donor density due to poorer environmental suitability and greater disturbance history. Our results demonstrate a differential shift in reproductive assurance and inbreeding costs in mahogany, driven by exploitation history and contemporary landscape context.

The complimentary role of genetic and ecological data in understanding population structure: a case study using moose (Alces alces) - L. A. Finnegan; P. J. Wilson; G. N. Price; S. J. Lowe; B. R. Patterson; M.-J. Fortin; D. L. Murray (European Journal of Wildlife Research, 2012)

Oceanographic forcing of nutrient uptake and release over a fringing coral reef - Alex S. J. Wyatt; James L. Falter; Ryan J. Lowe; Stuart Humphries; Anya M. Waite (Limnology and Oceanography, 2012)
Nitrate and nitrite (NO x ) and phosphate (PO 4 ) dynamics over Ningaloo Reef, Western Australia, are shown to depend on oceanographic forcing of coupled mass transfer limited (MTL) gross uptake and gross release from remineralized oceanic particulate organic matter (POM). Estimates of gross release rates increased significantly with increasing POM uptake and were of the same order as gross uptake rates. Gross uptake rates increased significantly with increasing oceanic concentrations and wave energy dissipation, were 35–80% higher over the reef crest (7–9 mmol NO x m −2 d −1 and 4–5 mmol PO 4 m −2 d −1 ), and were significantly correlated with independent estimates of POM‐mediated gross NO x uptake, supporting both MTL uptake and the strong role of oceanic POM supply. The relative supply of NO x and POM was linked to the seasonal dynamics of a regional current system. In late spring, upwelling associated with seasonally strong equator‐ward winds led to increased NO x concentrations (0.71 ± 0.2 µmol L −1 ), POM x and the reef was a net nutrient sink (5390 mmol NO x m −1 d −1 and 270 mmol PO 4 m −1 d −1 ). In contrast, during the autumn, NO x was low (0.16 ± 0.06 µmol L −1 ), but POM > NO x and the reef was a net nutrient source (−7060 mmol NO x m −1 d −1 and −730 mmol PO 4 m −1 d −1 ). The autumn enhancement of oceanic POM supply to the reef can be attributed to a regional phytoplankton bloom associated with acceleration of the oligotrophic Leeuwin Current, which may result in a significant supply of dissolved nutrients to downstream communities.

Does lycopene offer human LDL any protection against myeloperoxidase activity? - Poh Yeong Chew; Lucy Riley; Daniel L. Graham; Khalid Rahman; Gordon M. Lowe (Molecular and Cellular Biochemistry, 2012)

Exploring high-end scenarios for local sea level rise to develop flood protection strategies for a low-lying delta—the Netherlands as an example - Caroline A. Katsman; A. Sterl; J. J. Beersma; H. W. van den Brink; J. A. Church; W. Hazeleger; R. E. Kopp; D. Kroon; J. Kwadijk; R. Lammersen; J. Lowe; M. Oppenheimer; et al. (Climatic Change, 2011)

Neuroanatomical targets of reboxetine and bupropion as revealed by pharmacological magnetic resonance imaging - Sakthivel Sekar; J. Van Audekerke; G. Vanhoutte; A. S. Lowe; A. M. Blamire; A. Van der Linden; T. Steckler; M. Shoaib; Marleen Verhoye (Psychopharmacology, 2011)

The Tyndall coastal simulator - Mustafa Mokrech; Susan Hanson; Robert J. Nicholls; Judith Wolf; Mike Walkden; Corentin M. Fontaine; Sophie Nicholson-Cole; Simon R. Jude; James Leake; Peter Stansby; Andrew R. Watkinson; Mark D. A. Rounsevell; et al. (Journal of Coastal Conservation, 2011)

Uptake of picophytoplankton, bacterioplankton and virioplankton by a fringing coral reef community (Ningaloo Reef, Australia) - N. L. Patten; A. S. J. Wyatt; R. J. Lowe; A. M. Waite (Coral Reefs, 2011)

Determining association networks in social animals: choosing spatial–temporal criteria and sampling rates - Hamed Haddadi; Andrew J. King; Alison P. Wills; Damien Fay; John Lowe; A. Jennifer Morton; Stephen Hailes; Alan M. Wilson (Behavioral Ecology and Sociobiology, 2011)

Ocean warming and acidification; implications for the Arctic brittlestar Ophiocten sericeum - Hannah L. Wood; J. I. Spicer; M. A. Kendall; D. M. Lowe; S. Widdicombe (Polar Biology, 2011)

Can a seed bank provide demographic and genetic rescue in a declining population of the endangered shrub Acacia pinguifolia? - Kym M. Ottewell; Doug Bickerton; Andrew J. Lowe (Conservation Genetics, 2011)

Erratum to: A model study of factors influencing projected changes in regional sea level over the twenty-first century - Anne K. Pardaens; J. M. Gregory; J. A. Lowe (Climate Dynamics, 2011)

A model study of factors influencing projected changes in regional sea level over the twenty-first century - Anne K. Pardaens; J. M. Gregory; J. A. Lowe (Climate Dynamics, 2011)

Short-term coherency between gross primary production and community respiration in an algal-dominated reef flat - J. L. Falter; M. J. Atkinson; D. W. Schar; R. J. Lowe; S. G. Monismith (Coral Reefs, 2011)

The analysis of immunological profiles in wild animals: a case study on immunodynamics in the field vole, Microtus agrestis - JOSEPH A. JACKSON; MICHAEL BEGON; RICHARD BIRTLES; STEVE PATERSON; IDA M. FRIBERG; AMY HALL; ANN LOWE; CATRIONA RALLI; ANDREW TURNER; MALGORZATA ZAWADZKA; JANETTE E. BRADLEY (Molecular Ecology, 2011)
A revolutionary advance in ecological immunology is that postgenomic technologies now allow molecular mediators defined in laboratory models to be measured at the mRNA level in field studies of many naturally occurring species. Here, we demonstrate the application of such an approach to generate meaningful immunological profiles for wild mammals. We sampled a natural field vole population across the year ( n = 307) and developed a battery of cellular assays in which functionally different pro‐ and anti‐inflammatory signalling responses (transcription factors and cytokines) were activated and quantified by Q‐PCR. Temporal trends were the strongest feature in the expression data, although some life history stages (mating vs. nonmating males and pregnant females) were also associated with significant variation. There was a striking set of significant negative associations between inflammatory mediators and condition indices reflecting packed erythrocyte volume and relative liver size, spleen size and splenocyte count. Grouped (principal component) measures of inflammatory and anti‐inflammatory expression were high in winter, with minima in the breeding season that occurred earlier for grouped anti‐inflammatory responses than for grouped inflammatory responses. Some individual immunological mediators also showed patterns unrelated to the breeding season or annual periodic cues. For example, interferon regulatory factor 5 (IRF5) expression declined throughout the study period, indicating a systematic trend in antimicrobial defences. Pinpointing the causes and consequences of such variation may help identify underlying environmental drivers of individual fitness and demographic fluctuation.

Neuroadaptive responses to citalopram in rats using pharmacological magnetic resonance imaging - Sakthivel Sekar; M. Verhoye; J. Van Audekerke; G. Vanhoutte; Andrew S. Lowe; Andrew M. Blamire; Thomas Steckler; A. Van der Linden; Mohammed Shoaib (Psychopharmacology, 2011)

Thresholds for irreversible decline of the Greenland ice sheet - Jeff Ridley; Jonathan M. Gregory; Philippe Huybrechts; Jason Lowe (Climate Dynamics, 2010)

Erratum to: Effect of Surface Charge of Immortalized Mouse Cerebral Endothelial Cell Monolayer on Transport of Charged Solutes - Wei Yuan; Guanglei Li; Eun Seok Gil; Tao Lu Lowe; Bingmei M. Fu (Annals of Biomedical Engineering, 2010)

Interaction of ocean acidification and temperature; the high cost of survival in the brittlestar Ophiura ophiura - Hannah L. Wood; J. I. Spicer; D. M. Lowe; S. Widdicombe (Marine Biology, 2010)

Foraging ecology of Cookiecutter Sharks (Isistius brasiliensis) on pelagic fishes in Hawaii, inferred from prey bite wounds - Yannis P. Papastamatiou; Brad M. Wetherbee; John O’Sullivan; Gwen D. Goodmanlowe; Christopher G. Lowe (Environmental Biology of Fishes, 2010)

Population genetic structure of the round stingray Urobatis halleri (Elasmobranchii: Rajiformes) in southern California and the Gulf of California - S. M. Plank; C. G. Lowe; K. A. Feldheim; R. R. Wilson; J. A. Brusslan (Journal of Fish Biology, 2010)
The round stingray, Urobatis halleri , is a viviparous elasmobranch that inhabits inshore, benthic habitats ranging from the western U.S.A. to Panama. The population genetic structure of this species was inferred with seven polymorphic microsatellite loci in samples collected at three sites in coastal southern California, one near Santa Catalina Island, California and one in the eastern Gulf of California. Urobatis halleri is relatively common, but little is known of its movement patterns or population structure. Small F ST values (−0·0017 to 0·0005) suggested little structure among coastal populations of southern and Baja California. The population sampled at Santa Catalina Island, which is separated by a deep‐water channel from the coastal sites, however, was significantly divergent (large F ST , 0·0251) from the other populations, suggesting low connectivity with coastal populations. The Santa Catalina Island population also had the lowest allele richness and lowest average heterozygosity, suggesting recent population bottlenecks in size.

Modelling chemistry in the nocturnal boundary layer above tropical rainforest and a generalised effective nocturnal ozone deposition velocity for sub-ppbv NOx conditions - Thomas A. M. Pugh; James Ryder; A. Robert MacKenzie; Sarah J. Moller; James D. Lee; Carole Helfter; Eiko Nemitz; Douglas Lowe; C. Nicholas Hewitt (Journal of Atmospheric Chemistry, 2010)

Climate change, conservation and management: an assessment of the peer-reviewed scientific journal literature - Adam Felton; Joern Fischer; David B. Lindenmayer; Rebecca Montague-Drake; Arianne R. Lowe; Debbie Saunders; Annika M. Felton; Will Steffen; Nicola T. Munro; Kara Youngentob; Jake Gillen; Phil Gibbons; et al. (Biodiversity and Conservation, 2009)

Scale‐dependent effects of habitat on movements and path structure of reef sharks at a predator‐dominated atoll - Yannis P. Papastamatiou; Christopher G. Lowe; Jennifer E. Caselle; Alan M. Friedlander (Ecology, 2009)
The effects of habitat on the ecology, movements, and foraging strategies of marine apex predators are largely unknown. We used acoustic telemetry to quantify the movement patterns of blacktip reef sharks ( Carcharhinus melanopterus ) at Palmyra Atoll National Wildlife Refuge, in the Pacific Ocean. Sharks had relatively small home ranges over a timescale of days to weeks (0.55 ± 0.24 km 2 ) and showed strong site fidelity to sand‐flat ledges within the west lagoon over a three‐year period. Sharks showed evidence of diel and tidal movements, and they utilized certain regions of the west lagoon disproportionately. There were ontogenetic shifts in habitat selection, with smaller sharks showing greater selection for sand‐flat habitats, and pups (total length 35–61 cm) utilizing very shallow waters on sand‐flats, potentially as nursery areas. Adult sharks selected ledge habitats and had lower rates of movement when over sand‐flats and ledges than they did over lagoon waters. Fractal analysis of movements showed that over periods of days, sharks used patches that were 3–17% of the scale of their home range. Repeat horizontal movements along ledge habitats consisted of relatively straight movements, which theoretical models consider the most efficient search strategy when forage patches may be spatially and temporally unpredictable. Although sharks moved using a direct walk while in patches, they appeared to move randomly between patches. Microhabitat quantity and quality had large effects on blacktip reef shark movements, which have consequences for the life‐history characteristics of the species and potentially the spatial distribution of behaviorally mediated effects on lower trophic levels throughout the Palmyra ecosystem.

Variation in recombination rates across Vitis species - Kristin M. Lowe; Summaira Riaz; M. Andrew Walker (Tree Genetics & Genomes, 2009)

Over-expression of a gibberellin 2-oxidase gene from Phaseolus coccineus L. enhances gibberellin inactivation and induces dwarfism in Solanum species - C. Dijkstra; E. Adams; A. Bhattacharya; A. F. Page; P. Anthony; S. Kourmpetli; J. B. Power; K. C. Lowe; S. G. Thomas; P. Hedden; A. L. Phillips; M. R. Davey (Plant Cell Reports, 2008)

Testing the role of genetic factors across multiple independent invasions of the shrub Scotch broom ( Cytisus scoparius ) - MING KANG; YVONNE M. BUCKLEY; ANDREW J. LOWE (Molecular Ecology, 2007)
Knowledge of the introduction history of invasive plants informs on theories of invasiveness and assists in the invasives management. For the highly successful invasive shrub Scotch broom, Cytisus scoparius , we analysed a combination of nuclear and chloroplast microsatellites for eight native source regions and eight independent invasion events in four countries across three continents. We found that two exotic Australian populations came from different sources, one of which was derived from multiple native populations, as was an invasive sample from California. An invasive population from New Zealand appeared to be predominantly sourced from a single population, either from the native or exotic ranges. Four invasive populations from Chile were genetically differentiated from the native range samples analysed here and so their source of introduction could not be confirmed, but high levels of differentiation between the Chilean populations suggested a combination of different sources. This extensive global data set of replicated introductions also enabled tests of key theories of invasiveness in relation to genetic diversity. We conclude that invasive populations have similar levels of high genetic diversity to native ranges; levels of admixture may vary across invasive populations so admixture does not appear to have been an essential requirement for invasion; invasive and native populations exhibit similar level of genetic structure indicating similar gene flow dynamics for both types of populations. High levels of diversity and multiple source populations for invasive populations observed here discount founder effects or drift as likely explanations for previously observed seed size differences between ranges. The high levels of genetic diversity, differential and source admixture identified for most exotic populations are likely to limit the ability to source biocontrol agents from the native region of origin of invasive populations.

Vegetation and climate of Auckland, New Zealand, since ca. 32 000 cal. yr ago: support for an extended LGM - Rewi M. Newnham; David J. Lowe; Teresa Giles; Brent V. Alloway (Journal of Quaternary Science, 2007)
Auckland occupies a climatically sensitive position close to a major biogeographic boundary in the southern mid‐latitudes. A new pollen record from Kohuora maar crater, Auckland, displays vegetation and climatic changes for the past ca. 32 000 years. Of particular interest are the inferred climatic patterns for the first part of the interval, encompassing the Last Glacial Maximum (LGM). The Kohuora record corresponds closely with pollen records from other Auckland sites indicating that the patterns observed are at least regional in extent. It is also broadly consistent with a variety of palaeoenvironmental evidence from across New Zealand, including the glacial record from Westland, other palynological records from North Island, other palaeoecological records from the South Island, and aeolian quartz sequences from western North Island. These records show that glacial conditions prevailed across most, if not all, of New Zealand during the interval ca. 29–19 k cal. yr BP, longer and earlier than the LGM sensu stricto . We suggest that the term extended LGM (eLGM) may be more appropriate for the New Zealand region. Within this predominantly cold interval, the Auckland pollen records indicate a climatic amelioration for the interval ca. 26–24 k cal. yr BP, also consistent with other palaeocological data from Canterbury, that fall within a period of climate amelioration recognised between the first two eLGM glacial advances in Westland. We refer to this warming interval as the eLGM Interstadial. The ca. 27 k cal. yr BP Kawakawa/Oruanui tephra is instrumental in most of these inter‐site comparisons and occurs after the first peak of eLGM cooling in a short‐lived comparatively mild phase. A subsequent return to apparently colder climate in the Auckland records may indicate a volcanic cooling effect or, more likely, widespread landscape disturbance following this major eruption event. Strong correspondence between biotic responses, glacial fluctuations and aeolian quartz deposition linked to major shifts in strength and latitudinal extent of the southern westerlies suggest that both the eLGM and eLGM Interstadial may be more widely registered, at least across the Southern Ocean. Support for this assertion comes from parallel investigations in western and southernmost South America and isotopic and palaeoecological records from Southern Ocean marine cores. Recent reconstructions of the globally averaged ice‐equivalent sea‐level history are in line with this evidence from the Southern Hemisphere, suggesting that the eLGM may have a global registration. In light of these observations, we suggest a re‐examination of the defined timing of the LGM along with renewed effort to establish climatic patterns during this period and understand their causes. Copyright © 2007 John Wiley & Sons, Ltd.

Microarray analysis of the hyperthermophilic archaeon Pyrococcus furiosus exposed to gamma irradiation - Ernest Williams; Todd M. Lowe; Jeffrey Savas; Jocelyne DiRuggiero (Extremophiles, 2007)

Microarray analysis of the hyperthermophilic archaeon Pyrococcus furiosus exposed to gamma irradiation - Ernest Williams; Todd M. Lowe; Jeffrey Savas; Jocelyne DiRuggiero (Extremophiles, 2007)

Test of AMS 14 C dating of pollen concentrates using tephrochronology - Rewi M. Newnham; Marcus J. Vandergoes; Mark H. Garnett; David J. Lowe; Christine Prior; Peter C. Almond (Journal of Quaternary Science, 2007)
Previous attempts to radiocarbon date sediments >10 kyr from the high rainfall region of Westland, New Zealand, a critical location for investigation of interhemispheric patterns of climate change, have been problematic. This study, building on recent work by Vandergoes and Prior ( 2003 ), shows that AMS 14 C dating of pollen concentrates has potential to provide more reliable ages than other sediment constituents, including plant macrofossils. The method was applied to sediments from three sites containing the 22.6k 14 C yr Kawakawa Tephra, which provided an independent test of the 14 C ages. Although some minor laboratory contamination was detected in tests on background standards, the modelled relationship between sample mass and measured 14 C content permitted an appropriate correction to be determined. Improved pollen concentrations derived by density separation between 1.4 and 1.2 specific gravity and sieving in the range 10–50 μm provided either older ages than other fractions of the same sample or, where in situ contamination was not evident, equivalent ages. Differences in degree of in situ contamination between depositional environments indicated that, in Westland, lake sites may be less susceptible to contamination by younger carbon than peat sites, where this process may be facilitated by root penetration into underlying sediments. Copyright © 2006 John Wiley & Sons, Ltd.

Towards a climate event stratigraphy for New Zealand over the past 30 000 years (NZ‐INTIMATE project) - Brent V. Alloway; David J. Lowe; David J. A. Barrell; Rewi M. Newnham; Peter C. Almond; Paul C. Augustinus; Nancy A. N. Bertler; Lionel Carter; Nicola J. Litchfield; Matt S. McGlone; Jamie Shulmeister; Marcus J. Vandergoes; et al. (Journal of Quaternary Science, 2007)
It is widely recognised that the acquisition of high‐resolution palaeoclimate records from southern mid‐latitude sites is essential for establishing a coherent picture of inter‐hemispheric climate change and for better understanding of the role of Antarctic climate dynamics in the global climate system. New Zealand is considered to be a sensitive monitor of climate change because it is one of a few sizeable landmasses in the Southern Hemisphere westerly circulation zone, a critical transition zone between subtropical and Antarctic influences. New Zealand has mountainous axial ranges that amplify the climate signals and, consequently, the environmental gradients are highly sensitive to subtle changes in atmospheric and oceanic conditions. Since 1995, INTIMATE has, through a series of international workshops, sought ways to improve procedures for establishing the precise ages of climate events, and to correlate them with high precision, for the last 30 000 calendar years. The NZ‐INTIMATE project commenced in late 2003, and has involved virtually the entire New Zealand palaeoclimate community. Its aim is to develop an event stratigraphy for the New Zealand region over the past 30 000 years, and to reconcile these events against the established climatostratigraphy of the last glacial cycle which has largely been developed from Northern Hemisphere records (e.g. Last Glacial Maximum (LGM), Termination I, Younger Dryas). An initial outcome of NZ‐INTIMATE has been the identification of a series of well‐dated, high‐resolution onshore and offshore proxy records from a variety of latitudes and elevations on a common calendar timescale from 30 000 cal. yr BP to the present day. High‐resolution records for the last glacial coldest period (LGCP) (including the LGM sensu stricto ) and last glacial–interglacial transition (LGIT) from Auckland maars, Kaipo and Otamangakau wetlands on eastern and central North Island, marine core MD97‐2121 east of southern North Island, speleothems on northwest South Island, Okarito wetland on southwestern South Island, are presented. Discontinuous (fragmentary) records comprising compilations of glacial sequences, fluvial sequences, loess accumulation, and aeolian quartz accumulation in an andesitic terrain are described. Comparisons with ice‐core records from Antarctica (EPICA Dome C) and Greenland (GISP2) are discussed. A major advantage immediately evident from these records apart from the speleothem record, is that they are linked precisely by one or more tephra layers. Based on these New Zealand terrestrial and marine records, a reasonably coherent, regionally applicable, sequence of climatically linked stratigraphic events over the past 30 000 cal. yr is emerging. Three major climate events are recognised: (1) LGCP beginning at ca. 28 000 cal. yr BP, ending at Termination I, ca. 18 000 cal. yr BP, and including a warmer and more variable phase between ca. 27 000 and 21 000 cal. yr BP, (2) LGIT between ca. 18 000 and 11 600 cal. yr BP, including a Lateglacial warm period from ca. 14 800 to 13 500 cal. yr BP and a Lateglacial climate reversal between ca. 13 500 and 11 600 cal. yr BP, and (3) Holocene interglacial conditions, with two phases of greatest warmth between ca. 11 600 and 10 800 cal. yr BP and from ca. 6 800 to 6 500 cal. yr BP. Some key boundaries coincide with volcanic tephras. Copyright © 2007 John Wiley & Sons, Ltd.

Public Perceptions of Forest Management in North Central Arizona: The Paradox of Demanding More Involvement but Allowing Limits to Legal Action - David M. Ostergren; Kimberly A. Lowe; Jesse B. Abrams; Elizabeth J. Ruther (Journal of Forestry, 2006)
National-level forest policy is changing in response to social pressure to “improve forest health.” A particularly fierce public debate surrounds the forest health impacts of administrative appeals, lawsuits, public involvement, and federal agency ability to balance managerial efficiency, ecological health, and social expectations. A self-administered mail survey was conducted in 2003 to assess public opinion on litigation and forest restoration in north central Arizonan communities in the ponderosa pine ecosystem. Although results indicate some support for limits to the right to file suit, appeal, and review environmental decisions, an overwhelming number of respondents indicate a strong desire to be more informed and involved in forest management decisions.

The chronology of abrupt climate change and Late Upper Palaeolithic human adaptation in Europe - S. P. E. Blockley; S. M. Blockley; R. E. Donahue; C. S. Lane; J. J. Lowe; A. M. Pollard (Journal of Quaternary Science, 2006)
This paper addresses the possible connections between the onset of human expansion in Europe following the Last Glacial Maximum, and the timing of abrupt climate warming at the onset of the Lateglacial (Bölling/Allerød) Interstadial. There are opposing views as to whether or not human populations and activities were directly ‘forced’ by climate change, based on different comparisons between archaeological and environmental data. We review the geochronological assumptions and approaches on which data comparisons have been attempted in the past, and argue that the uncertainties presently associated with age models based on calibrated radiocarbon dates preclude robust testing of the competing models, particularly when comparing the data to non‐radiocarbon‐based timescales such as the Greenland ice core records. The paper concludes with some suggestions as to the steps that will be necessary if more robust tests of the models are to be developed in the future. Copyright © 2006 John Wiley & Sons, Ltd.

Genetic linkage map of the interspecific grape rootstock cross Ramsey (Vitis champinii) × Riparia Gloire (Vitis riparia) - K. M. Lowe; M. A. Walker (Theoretical and Applied Genetics, 2006)

Food habits and ontogenetic changes in the diet of the sandbar shark, Carcharhinus plumbeus, in Hawaii - W. David McElroy; Bradley M. Wetherbee; Carolyn S. Mostello; Christopher G. Lowe; Gerald L. Crow; Richard C. Wass (Environmental Biology of Fishes, 2006)

Geographic patterns in the demersal ichthyofauna of the Aleutian Islands - E. A. LOGERWELL; K. AYDIN; S. BARBEAUX; E. BROWN; M. E. CONNERS; S. LOWE; J. W. ORR; I. ORTIZ; R. REUTER; P. SPENCER (Fisheries Oceanography, 2005)
The goals of this research were to investigate geographic patterns in the Aleutian Island region's demersal ichthyofauna and to determine whether they reflected the physical and biological oceanographic patterns documented by other authors in this volume. The analyses were structured according to the level of organization: at the community level, patterns in species occurrence and community structure were investigated; at the population level, distribution and abundance were examined; at the individual level, food habits and growth were studied. There were step‐changes in species occurrence, diversity, population distribution and food habits at Samalga Pass and at sites farther west. These longitudinal trends indicated physical and biological variation along the length of the Aleutian Islands chain; however, depth‐related patterns were as common as longitudinal patterns in demersal fish distribution. In addition, high catches of patchily distributed species occurred in areas expected to be biological ‘hot spots’ because of increased productivity and prey availability. These patterns suggest linkages between demersal fish ecology and the biophysical processes described by other authors in this volume and indicate that inter‐disciplinary research is needed to elucidate the underlying mechanisms.

Identification of a neurofilament-like protein in the protocerebral tract of the crab Ucides cordatus - Clynton Lourenço Corrêa; Simone Florim da Silva; Jennifer Lowe; Giovane G. Tortelote; Marcelo Einicker-Lamas; Ana M. Blanco Martinez; Silvana Allodi (Cell and Tissue Research, 2004)

Efficient large-scale development of microsatellites for marker and mapping applications in Brassica crop species - A. J. Lowe; C. Moule; M. Trick; K. J. Edwards (Theoretical and Applied Genetics, 2004)

Qualification of analytical instruments for use in the pharmaceutical industry: A scientific approach - Surendra K. Bansal; Thomas Layloff; Ernest D. Bush; Marta Hamilton; Edward A. Hankinson; John S. Landy; Stephen Lowes; Moheb M. Nasr; Paul A. St. Jean; Vinod P. Shah (AAPS PharmSciTech, 2004)

Qualification of analytical instruments for use in the pharmaceutical industry: A scientific approach - Surendra K. Bansal; Thomas Layloff; Ernest D. Bush; Marta Hamilton; Edward A. Hankinson; John S. Landy; Stephen Lowes; Moheb M. Nasr; Paul A. St. Jean; Vinod P. Shah (AAPS PharmSciTech, 2004)

Bayesian analysis of radiocarbon chronologies: examples from the European Late‐glacial - S. P. E. Blockley; J. J. Lowe; M. J. C. Walker; A. Asioli; F. Trincardi; G. R. Coope; R. E. Donahue (Journal of Quaternary Science, 2004)
Although there are many Late‐glacial (ca. 15 000–11 000 cal. yr BP) proxy climate records from northwest Europe, some analysed at a very high temporal resolution (decadal to century scale), attempts to establish time‐stratigraphical correlations between sequences are constrained by problems of radiocarbon dating. In an attempt to overcome some of these difficulties, we have used a Bayesian approach to the analysis of radiocarbon chronologies for two Late‐glacial sites in the British Isles and one in the Adriatic Sea. The palaeoclimatic records from the three sites were then compared with that from the GRIP Greenland ice‐core. Although there are some apparent differences in the timing of climatic events during the early part of the Late‐glacial (pre‐14 000 cal. yr BP), the results suggest that regional climatic changes appear to have been broadly comparable between Greenland, the British Isles and the Adriatic during the major part of the Late‐glacial (i.e. between 14 000 and 11 000 cal. yr BP). The advantage of using the Bayesian approach is that it provides a means of testing the reliability of Late‐glacial radiocarbon chronologies that is independent of regional chronostratigraphical (climatostratigraphical) frameworks. It also uses the full radiocarbon inventory available for each sequence and makes explicit any data selection applied. Potentially, therefore, it offers a more ‘objective’ basis for comparing regional radiocarbon chronologies than the conventional approaches that have been used hitherto. Copyright © 2004 John Wiley & Sons, Ltd.

Tephrochronology of last termination sequences in Europe: a protocol for improved analytical precision and robust correlation procedures (a joint SCOTAV–INTIMATE proposal) - Chris S. M. Turney; J. John Lowe; Siwan M. Davies; Valerie Hall; David J. Lowe; Stefan Wastegård; Wim Z. Hoek; Brent Alloway (Journal of Quaternary Science, 2004)
The precise sequence of events during the Last Termination (18 000–9000 ka 14 C yr BP), and the extent to which major environmental changes were synchronous, are difficult to establish using the radiocarbon method alone because of serious distortions of the radiocarbon time‐scale, as well as the influences of site‐specific errors that can affect the materials dated. Attention has therefore turned to other methods that can provide independent tests of the chronology and correlation of events during the Last Termination. With emphasis on European sequences, we summarise here the potential of tephrostratigraphy and tephrochronology to fulfil this role. Recent advances in the detection and analysis of ‘hidden’ tephra layers (cryptotephra) indicate that some tephras of Last Termination age are much more widespread in Europe than appreciated hitherto, and a number of new tephra deposits have also been identified. There is much potential for developing an integrated tephrochronological framework for Europe, which can help to underpin the overall chronology of events during the Last Termination. For that potential to be realised, however, there needs to be a more systematic and robust analysis of tephra layers than has been the practice in the past. We propose a protocol for improving analytical and reporting procedures, as well as the establishment of a centralised data base of the results, which will provide an important geochronological tool to support a diverse range of stratigraphical studies, including opportunities to reassess volcanic hazards. Although aimed primarily at Europe, the protocol proposed here is of equal relevance to other regions and periods of interest. Copyright © 2004 John Wiley & Sons, Ltd.

A coherent high‐precision radiocarbon chronology for the Late‐glacial sequence at Sluggan Bog, Co. Antrim, Northern Ireland - J. J. Lowe; M. J. C. Walker; E. M. Scott; D. D. Harkness; C. L. Bryant; S. M. Davies (Journal of Quaternary Science, 2004)
Seventy‐five radiocarbon dates are presented from Sluggan Bog in Co. Antrim, Northern Ireland. The Holocene peats are underlain by Late‐glacial sediments, which also appear to have accumulated largely in a mire environment. The radiocarbon dates, from the Late‐glacial and early Holocene part of the profile, were obtained from the humic and humin fractions of the sedimentary matrix, and from plant macrofossils. The last‐named were dated by AMS and the sediment samples by radiometric (beta counting) methods. Age–depth models for the three dating series show a very high level of agreement between the two fractions and the macrofossils. No statistically significant difference is found between the beta counting and AMS results. Three tephras were located in the profile, the uppermost of which is in a stratigraphical position suggestive of the Vedde Ash, but the geochemical and radiocarbon evidence do not support this interpretation. The lower ashes are in the correct stratigraphical position for the Laacher See and Borrobol tephras, attributions substantiated by the radiocarbon evidence, but not by the geochemical data. The Sluggan sequence has generated one of the most internally consistent radiocarbon chronologies for any Late‐glacial site in the British Isles, and it is suggested that in future more effort should be devoted to the search for, and analysis of, Late‐glacial mire sequences, rather than the limnic records that have formed the principal focus of Late‐glacial investigations hitherto. Copyright © 2004 John Wiley & Sons, Ltd.

RhoA induction by functional overload and nandrolone decanoate administration in rat skeletal muscle - Joseph M. McClung; Won J. Lee; Raymond W. Thompson; Larry L. Lowe; James A. Carson (Pflügers Archiv - European Journal of Physiology, 2003)

Causes of Sediment Toxicity to Mytilus galloprovincialis in San Francisco Bay, California - B. M. Phillips; B. S. Anderson; J. W. Hunt; B. Thompson; S. Lowe; R. Hoenicke; R. Tjeerdema (Archives of Environmental Contamination and Toxicology, 2003)

Molecular analysis of two cytochrome P450 monooxygenase genes required for paxilline biosynthesis in Penicillium paxilli, and effects of paxilline intermediates on mammalian maxi-K ion channels - L. K. McMillan; R. L. Carr; C. A. Young; J. W. Astin; R. G. T. Lowe; E. J. Parker; G. B. Jameson; S. C. Finch; C. O. Miles; O. B. McManus; W. A. Schmalhofer; M. L. Garcia; et al. (Molecular Genetics and Genomics, 2003)

Erratum - Daniel J. Becker; Jay T. Myers; Melissa M. Ruff; Peter L. Smith; Brenda W. Gillespie; David W. Ginsburg; John B. Lowe (Mammalian Genome, 2003)

How much effort is required to isolate nuclear microsatellites from plants? - J. Squirrell; P. M. Hollingsworth; M. Woodhead; J. Russell; A. J. Lowe; M. Gibby; W. Powell (Molecular Ecology, 2003)
The attributes of codominance, reproducibility and high resolution have all contributed towards the current popularity of nuclear microsatellites as genetic markers in molecular ecological studies. One of their major drawbacks, however, is the development phase required to obtain working primers for a given study species. To facilitate project planning, we have reviewed the literature to quantify the workload involved in isolating nuclear microsatellites from plants. We highlight the attrition of loci at each stage in the process, and the average effort required to obtain 10 working microsatellite primer pairs.

Anthropogenic climate change for 1860 to 2100 simulated with the HadCM3 model under updated emissions scenarios - T. C. Johns; J. M. Gregory; W. J. Ingram; C. E. Johnson; A. Jones; J. A. Lowe; J. F. B. Mitchell; D. L. Roberts; D. M. H. Sexton; D. S. Stevenson; S. F. B. Tett; M. J. Woodage (Climate Dynamics, 2003)

Chromosomal regions controlling resistance to gastro-intestinal nematode infections in mice - Fuad A. Iraqi; Jerzy M. Behnke; David M. Menge; Anna Lowe; Alan J. Teale; John P. Gibson; Leyden R. Baker; Derek Wakelin (Mammalian Genome, 2003)

Characterisation of the expression of a novel constitutive maize promoter in transgenic wheat and maize - S. Rasco-Gaunt; D. Liu; C. Li; A. Doherty; K. Hagemann; A. Riley; T. Thompson; C. Brunkan; M. Mitchell; K. Lowe; E. Krebbers; P. Lazzeri; et al. (Plant Cell Reports, 2003)

Strain-specific modification of lethality in fucose-deficient mice - Daniel J. Becker; Jay T. Myers; Melissa M. Ruff; Peter L. Smith; Brenda W. Gillespie; David W. Ginsburg; John B. Lowe (Mammalian Genome, 2003)

Comparison of results from several AOGCMs for global and regional sea-level change 1900-2100 - J. M. Gregory; J. A. Church; G. J. Boer; K. W. Dixon; G. M. Flato; D. R. Jackett; J. A. Lowe; S. P. O'Farrell; E. Roeckner; G. L. Russell; R. J. Stouffer; M. Winton (Climate Dynamics, 2001)

Changes in the occurrence of storm surges around the United Kingdom under a future climate scenario using a dynamic storm surge model driven by the Hadley Centre climate models - J. A. Lowe; J. M. Gregory; R. A. Flather (Climate Dynamics, 2001)

Identification and significance of a visible, basalt‐rich Vedde Ash layer in a Late‐glacial sequence on the Isle of Skye, Inner Hebrides, Scotland - Siwan M. Davies; Chris S. M. Turney; J. John Lowe (Journal of Quaternary Science, 2001)
This paper reports the discovery of a visible, tephra horizon of Late‐glacial age from the site of Loch Ashik in the Isle of Skye, the Inner Hebrides, Scotland. Although the tephra shards have a bimodal geochemical composition identical to that of the Vedde Ash (a well known marker horizon within Late‐glacial sequences. The horizon at Ashik is dominated by basaltic shards and devitrified tephra shards, giving the layer its characteristic black colour. Only rhyolitic shards have previously been reported from Vedde Ash horizons in the British Isles. This new evidence raises some important questions about the factors that govern the distribution and accumulation of basaltic tephra, and about the methods used to detect ash shards in basins distal to centres of volcanic activity. Copyright © 2001 John Wiley & Sons, Ltd.

Movement Patterns, Habitat Utilization, Home Range Size and Site Fidelity of Whitesaddle Goatfish, Parupeneus Porphyreus, In a Marine Reserve - Carl G. Meyer; Kim N. Holland; Bradley M. Wetherbee; Christopher G. Lowe (Environmental Biology of Fishes, 2000)

Chemistry of Leichhardt's Grasshopper, Petasida ephippigera, and its Host Plants, Pityrodia jamesii, P. ternifolia, and P. pungens - Mary T. Fletcher; Lynette M. Lowe; William Kitching; Wilfried A. König (Journal of Chemical Ecology, 2000)

Ternary Gd(III)L-HSA adducts: evidence for the replacement of inner-sphere water molecules by coordinating groups of the protein. Implications for the design of contrast agents for MRI - S. Aime; E. Gianolio; E. Terreno; G. B. Giovenzana; R. Pagliarin; M. Sisti; G. Palmisano; M. Botta; M. P. Lowe; D. Parker (JBIC Journal of Biological Inorganic Chemistry, 2000)

Conservation genetics of bush mango from central/west Africa: implications from random amplified polymorphic DNA analysis - A. J. Lowe; A. C. M. Gillies; J. Wilson; I. K. Dawson (Molecular Ecology, 2000)
Genetic variation was assessed in the two bush mango species, Irvingia gabonensis and I. wombolu , valuable multipurpose fruit trees from central and west Africa that are currently undergoing domestication. A total of 130 individuals sampled from Cameroon, Nigeria and Gabon were analysed using 74 random amplified polymorphic DNAs (RAPDs). Significant genetic integrity was found in the two morphologically similar species (among‐species analysis of molecular variance [ amova ] variance component 25.8%, P amova variance component 9.8%, P I. wombolu , and in southern Nigeria, southern Cameroon and central Gabon for I. gabonensis . The possible reasons for this distribution of genetic variation are discussed, but it may reflect evolutionary history, as these populations occur in areas of postulated Pleistocene refugia. The application of these results to domestication programmes and, in the light of extensive deforestation in the region, conservation approaches, is discussed.

Evidence for short-lived oscillations in the biological records from the sediments of Lago Albano (Central Italy) spanning the period ca. 28 to 17 k yr BP - Piero Guilizzoni; Aldo Marchetto; Andrea Lami; Frank Oldfield; Marina Manca; Claudio A. Belis; Anna M. Nocentini; Patrizia Comoli; Vivienne J. Jones; Steve Juggins; Christina Chondrogianni; Daniel Ariztegui; et al. (Journal of Paleolimnology, 2000)

Movements of tiger sharks ( Galeocerdo cuvier ) in coastal Hawaiian waters - K. N. Holland; B. M. Wetherbee; C. G. Lowe; C. G. Meyer (Marine Biology, 1999)

A stable transformation system for the ornamental plant, Datura meteloides D. C. - I. S. Curtis; J. B. Power; P. Hedden; D. A. Ward; A. Phillips; K. C. Lowe; M. R. Davey (Plant Cell Reports, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Regulation of carbohydrate and fatty acid utilization by L-carnitine during cardiac development and hypoxia - Salah Abdel-aleem; James St. Louis; Steven C. Hendrickson; Hesham M. El-Shewy; Khalifa El-Dawy; Doris A. Taylor; James E. Lowe (Molecular and Cellular Biochemistry, 1998)

Carbon dioxide-gassed fluorocarbon enhances micropropagation of rose (Rosa chinesis Jacq.) - J. Wardrop; K. C. Lowe; M. R. Davey; R. Marchant; J. B. Power (Plant Cell Reports, 1997)

Strategies for promoting division of cultured plant protoplasts: synergistic beneficial effects of haemoglobin (Erythrogen) and Pluronic F-68 - P. Anthony; K. C. Lowe; M. R. Davey; J. B. Power (Plant Cell Reports, 1997)

The use of microtephra horizons to correlate Late-glacial lake sediment successions in Scotland - Chris S. M. Turney; Douglas D. Harkness; J. John Lowe (Journal of Quaternary Science, 1997)

An acoustic tracking of a megamouth shark, Megachasma pelagios: a crepuscular vertical migrator - Donald R. Nelson; James N. McKibben; Wesley R. Strong; Christopher G. Lowe; Joseph A. Sisneros; Donna M. Schroeder; Robert J. Lavenberg (Environmental Biology of Fishes, 1997)

Stable carbon isotope variations in northwest Europe during the last glacial–interglacial transition - Chris S. M. Turney; David J. Beerling; Douglas D. Harkness; J. John Lowe; E. Marian Scott (Journal of Quaternary Science, 1997)

Exercise challenge in Antarctic fishes: do haematology and muscle metabolite levels limit swimming performance? - T. E. Lowe; R. M. G. Wells (Polar Biology, 1997)

Method for quantitating cholesterol in subfractions of serum lipoproteins separated by gradient gel electrophoresis - M. -L. Cheng; C. M. Kammerer; W. F. Lowe; B. Dyke; J. L. VandeBerg (Biochemical Genetics, 1988)

Method for quantitating cholesterol in subfractions of serum lipoproteins separated by gradient gel electrophoresis - M. -L. Cheng; C. M. Kammerer; W. F. Lowe; B. Dyke; J. L. VandeBerg (Biochemical Genetics, 1988)